Inerter-enhanced shared tuned sky corridor for seismic mitigation of twin buildings - Jian Song; Hao Ding; Huan Li; Ruisheng Ma (Soil Dynamics and Earthquake Engineering, 2026)

Bushen Yijing formula exerts chondroprotective effects in knee osteoarthritis via the ERα/PI3K/AKT signaling pathway: Insights from network pharmacology and experimental validation - Yu-Qing Zhai; Jian-Wei Lu; Qiang Yan; Jia-Wei Du; Yang-Shuo Ge; Min-Jun Zhao; Jian-Li Yin; Chun-Meng Huang; Ting-Ting Meng; Xin-Hui Huang; Liao-Lin Chen; Jia-Hui Luo; et al. (Tissue and Cell, 2026)

Unveiling TWC replacement benefits in in-use vehicles from a concentration-reactivity-toxicity perspective - Jie Yao; Xinping Yang; Yongdong Wang; Jian Wang; Yanjun Wang; Chao Peng; Hongfei Chen; Xin Li; Yunjing Wang; Yan Ding (Environmental Pollution, 2026)

Experimental study on the hydrodynamic response of a liquid-filled cylinder inclined into water - Jiahui Li; Cong Wang; Jian Bao; Wenpeng Li; Yu Liu; Wenzhi Yan; Yanyi Ding (Ocean Engineering, 2026)

Cu2O@Fe Prussian blue-integrated smartphone-assisted sensing strategy for hydroquinone and bisphenol A determination - Jian-Mei Chen; Yong-Qi Ding; Yan-Hong Zhou; Zi-Xuan Bai; Xiao-Tong Yang; Xin Huang; Shuai Li; Feng-Zhan Sun (Food Chemistry, 2026)

Pectin-driven microphase separation regulates hierarchical network formation and rheological functionality in egg yolk high-density lipoprotein fibril hydrogels - Jian Li; Xinyi Ju; Rui Chuang; Zihe Ding; Huajiang Zhang; Lina Xu; Jing Sun; Hanyu Li; Tong Zhang; He Zhang (Food Chemistry, 2026)

Steam explosion improves the flavor of Conger myriaster bone powder: Mechanistic insights from changes in physicochemical properties and flavor compounds - Ting Ye; Tianxiang Pi; Chao Ding; Xueyan Li; Jian Li; Chenghua Chen; Yujin Li; Yuanhui Zhao; Kangyu Wang; Xinxing Xu (Food Chemistry, 2026)

Diurnal differences in the effects of heat exposure on renal function: A randomized controlled crossover trial - Jintao Liu; Yuefang Li; Yarui Fan; Xiaojie Zou; Hung Chak Ho; Danfeng Zhang; Jing Zhang; Jian Song; Xu Wang; Xiuxiu Ding; Xiaoyu Jin; Lijuan Qiu; et al. (Environmental Research, 2026)

Characteristics and sources of organic vapors during O3 pollution in a megacity Wuhan in China: from hydrocarbons to highly oxidized molecules - Chong Liu; Xiaoxiao Li; Haoqian Wang; Linjun Li; Ning Ma; Xinchi Ye; Shan Xu; Jian Tan; Jin Peng; Rui Xia; Yi Zheng; Feiyue Mao; et al. (Atmospheric Environment, 2026)

Quantitative probabilistic assessment of nitrite from cooked meat products in Shandong population in China - Bo Huang; Jian Song; Hongshuang Ding; Fenghua Li (Regulatory Toxicology and Pharmacology, 2026)

A macin family antimicrobial peptide from Atrina pectinata exhibiting dual functions in direct bactericidal activity and hemocyte immune modulation - Yan-ru Chen; Kun-yu Zhao; Shun-xin Hu; Ding-long Yang; Xue-peng Li; Li-zhu Chen; Jian-min Zhao (Fish & Shellfish Immunology, 2026)

Environmental drivers of coordinated water-nitrogen management for maize resource use efficiency - Chenyan Li; Boyue Zhang; Xinlong Li; Xianqi Wang; Meiyi Feng; Shaozhong Kang; Taisheng Du; Ling Tong; Jian Kang; Jia Gao; Risheng Ding (European Journal of Agronomy, 2026)

Electronic structure modulation in Co-doped NiFe-LDH for efficient ethylene glycol oxidation in simulated seawater - Jiaming Ding; Tao Li; Yi Ma; Huan Ge; Ning Jian; Jialing Tang; Jing Yu; Jordi Arbiol; Haiting Wang; Luming Li; Andreu Cabot; Junshan Li (Chemical Engineering Journal, 2026)

PTPσ mediates the integration of grafted neuronal tissueoids with host neural pathways after complete spinal cord injury - Rui Mao; Yuan-Huan Ma; Jin-Yuan Xiao; Qing-Shuai Wei; Yin-Chun Zhao; Qi-Xing Hu; Hou-Ge Li; Ke-Jun Zhang; Lai-Jian Wang; Hui-Juan Shi; Li-Zhi Peng; Jun-Hua Wang; et al. (Science China Life Sciences, 2026)

Overlooked dark dissolved organic matter reveals the migration and transformation of carbon exports in surface and subsurface flows from cropland during rainfall - Guo Chen; Hao Wang; Qingwei Zhang; Chao Chang; Sisi Ye; Jian Wang; Fengbao Zhang; Zhenwei Yan; Biao Zhu; Ming Li; Ding He (Water Research, 2026)

Effects of ground motion types and rubber-sand-concrete damping layer on the seismic fragility of tunnel linings - Kaichen Li; Changdong Ding; Xiancheng Mei; Hao Sheng; Zhen Cui; Xuesong Cai; Jiajun Wu; Qian Sheng; Jian Chen (Transportation Geotechnics, 2026)

Retraction notice to “Environmental effect and spatiotemporal pattern of stable isotopes in precipitation on the transition zone between the Tibetan Plateau and arid region” [Sci. Total Environ. 749 (2020) 141559] - Gui Juan; Zongxing Li; Feng Qi; Yuan Ruifeng; Ning Tingting; Zhang Baijuan; Xue Jian; Gao Wende; Nan Fusen; Ding Weixuan; Yang Anle; Liang Pengfei (Science of The Total Environment, 2026)

Anthraquinone‑modulated oxygen disproportionation enables highly selective singlet oxygen generation for pollutant degradation - Yu Luo; Chenqi Lu; Chuang Xiao; Lin Ding; Mengyuan Zhao; Lingling Liu; Longshuai Zhang; Xibao Li; Fang Deng; Xubiao Luo; Jian-Ping Zou (Journal of Environmental Chemical Engineering, 2026)

Synergistic fermentation of functional microorganisms improves tobacco flavor quality by remodeling the microbial community and metabolite profiles - Wenlong Li; Wen Cai; Junxi Wang; Guiyuan Huang; Jian Chen; Zheng Peng; Juan Zhang; Wei Ding (Food Bioscience, 2026)

TianGong database—an open-source, ILCD entry-level life cycle unit process database of china - Ming Xu; Weiqiang Chen; Yutao Wang; Lei Shi; Zhi Cao; Huimin Chang; Chang Chen; Xiangbin Ding; Jianwei Du; Huabo Duan; Kai Fang; Cuiyang Feng; et al. (Journal of Industrial Ecology, 2026)

Population Decline, Inbreeding and Hybridization Shape the Genetic Vulnerability of a Critically Endangered Seabird - Guoling Chen; Chenqing Zheng; Lanhui Peng; Hongzhou Lin; Feng Dong; Shou‐Hsien Li; Yiwei Lu; Siyu Wang; Zhongyong Fan; Yinan Fu; Peng Ding; Jian Zhang; et al. (Molecular Ecology, 2026)
Many endangered species have been rescued from the brink of extinction, yet their long‐term viability remains uncertain due to the prolonged genetic consequences of severe bottlenecks. In particular, the combined effects of inbreeding and hybridization with closely related species remain poorly understood. Using a comparative conservation genomic framework, we investigated these issues in the Chinese crested tern ( Thalasseus bernsteini ), a critically endangered seabird once presumed extinct but which has increased to approximately 100 individuals over the past two decades and its close relative, the great crested tern ( T. bergii ). We demonstrate that the Chinese crested tern has experienced ongoing genetic erosion. Its prolonged population decline has intensified genetic drift and reduced the efficiency of purifying selection, resulting in genome‐wide accumulation of highly deleterious mutations. Highly inbred individuals also carry significantly more homozygous deleterious mutations than less inbred individuals. In both species, runs of homozygosity (ROH) show a relative enrichment of moderately and weakly deleterious mutations. Even more concerning, we found an enrichment of moderately and weakly deleterious mutations in putatively introgressed regions in both species, suggesting that occasional hybridization may have facilitated the spread of deleterious variants and could potentially compromise long‐term fitness. These findings highlight that severe bottlenecks have lasting genomic consequences and that both inbreeding and hybridization can increase the genetic vulnerability of small populations—underscoring the importance of management strategies that promote population growth and sustained genetic monitoring.

Variations in microbial community characteristics in runoff driven by maize growth stages under simulated rainfall in the semi-humid southern loess plateau of China - Zihan Yan; Guo Chen; Qingwei Zhang; Lihong Jia; Hao Wang; Chao Chang; Fengbao Zhang; Jian Wang; Ming Li; Ding He; Wei Zheng (CATENA, 2026)

A new amide alkaloid from the coculture liquid cultures of two grape endophytic fungi Penicillium sp. YPT103-2 and Penicillium sp. YPT104 - Yu-Qin Yang; Jin-Feng Cao; Juan-Juan Pu; Dong-Ping Li; Chuan-Mao Zhang; Zhi-Jian Wu; Jian-Hai Ding (Natural Product Research, 2026)

Luteolin ameliorates cigarette smoke-induced chronic obstructive pulmonary disease by modulating gut and lung microbiota and amino acid metabolism in C57Bl/6 mice - Tunyu Jian; Jiawei Huang; Fang Zhang; Weichen Zhang; Lina Zhou; Guanting Niu; Han Lv; Yanan Gai; Shijie Zhang; Weilin Li; Xiaoqin Ding; Jian Chen (Naunyn-Schmiedeberg's Archives of Pharmacology, 2026)

A potent TGF-β heterodimer orchestrates germ cell homeostasis in fish - Ming-Tao Wang; Chun Miao; Sheng Yang; Zhi Li; Meng-Di Zhu; Jie He; Miao Ding; Si-Wei Wu; Yang Zhang; Shun Li; Meng Lu; Peng Yu; et al. (Science Bulletin, 2026)

Spotted seabass Lateolabrax maculatus GSDMEa: a pyroptosis executor activated by CASP3/7 during bacterial infection - Xin Ding; Yuan Chen; Qingyue Wang; Zihao Yuan; Jian Zhang; Xuepeng Li; Hang Xu; Li Sun (Fish & Shellfish Immunology, 2026)

Cultivar-type driven fertilization strategies to decouple the trade-off between wheat yield and grain protein in dryland systems - Xuemei Zhang; Junfeng Xu; Zikang Guo; Cui Huang; Xiaohan Li; Zhiyuan Gao; Jiachuang Fang; Chenrui Liu; Yulan Ding; Jian Hou; Zilin Wang; Yang Feng; et al. (Field Crops Research, 2026)

Cross-domain microbial interactions mediate soil multifunctionality during crop growth stages - Guo Chen; Chao Chang; Zihan Yan; Hao Wang; Qingwei Zhang; Jian Wang; Ming Li; Wei Zheng; Ding He; Biao Zhu (Applied Soil Ecology, 2026)

Integrated Diagnosis and Therapy Using Flexible Contact Electrodes: Low-Voltage Irreversible Electroporation and Quantitative Assessment of Therapeutic Efficacy - Yuchen Cheng; Bowang Cheng; Jingyu Li; Zhuoqun Li; Fulai Lin; Yuan Qi; Haorui Xue; Jiawei Wang; Jian Lv; Fenggang Ren; Weidong Ding (Annals of Biomedical Engineering, 2026)

HuNT: A Reference Transcriptome Atlas for Human Normal Tissues - KaiLin Tang; XinYan Xu; XinYue Tang; XinWen Wu; ZiHao Li; Jian Gao; ShiYue Zhang; SaiFeng Mo; ZiKun Chen; Mou Zhang; Hao Ding; Yao Shi; et al. (Phenomics, 2026)
With the rapid development of transcriptomics technology, gene expression profiles of normal human tissues have been frequently utilized as valuable references to study aging and disease mechanisms. Although individual databases have been established, most human tissues remain under-sampled. Meanwhile, profiles from RNA-seq and microarray platforms must be analyzed separately due to inherent distribution bias, further weakening the statistical power of health samples. Here, we constructed a comprehensive transcriptome atlas for human normal tissues (HuNT) containing 29,769 samples covering 74 human normal tissue types or parts, 70% and 37% larger than those in the well-known GTEx database in terms of sample size and tissue diversity, respectively. More importantly, instead of separate calculation, integrative analysis has been enabled for hybrid samples across RNA-seq and microarray profiles per tissue type. Based on the largest human sample collection so far, HuNT provides the latest information on: (1) tissue-specific genes, (2) stably and highly expressed housekeeping genes for each tissue, (3) gene expression landscape across all human tissues, and (4) top correlated genes for a query in a specified tissue. A case study of four widely-acknowledged biomarkers is also illustrated in the paper. With future data accumulation, HuNT may be useful to provide not only gene expression landscapes in human normal tissues, but also benchmarks to derive interesting marker genes and even therapeutic targets. HuNT is now freely accessible at http://hunt.badd-cao.net/ .

Targeting flagellar-mediated virulence: The lipopeptide PW-1 suppresses pathogenicity in Ralstonia solanacearum - Hua Wang; Shili Li; Tao Liu; Lei He; Ruiyu Yang; Xiaoshuang Peng; Meng Liu; Nima Qiongda; Xiaoqi Wu; Qian Li; Jian Zhang; Huidi Liu; et al. (Pesticide Biochemistry and Physiology, 2026)

PCBs exposure and renal injury: comprehensive assessment strategy based upon TRAEC strategy - Zhiyuan Chen; Changqian Liu; Linlin Zhang; Jianrong Han; Xiaoyan Ding; Changshun Han; Sihao Zhu; Jiabao Cao; Jiaxin Song; Fucong Zhang; Jian Li; Zhenghong Zuo; et al. (Journal of Environmental Management, 2026)

Phylogeny, species diversity and divergence time of Diaporthe causing leaf blight on Acer palmatum in China - Yu Wan; De-Wei Li; Qiu-Yue Zhang; Yuan-Zhi Si; Jian-Wei Sun; Xiaolei Ding; Lin Huang; Li-Hua Zhu (Fungal Biology, 2026)

Translocation, degradation, distribution and processing of pesticides from soybeans to soybean sprouts - Kai Cui; Liping Fang; Ruiyan Ding; Wanru Su; Shuai Guan; Jingyun Liang; Teng Li; Junhua Liu; Jian Wang; Zhan Dong; Xiaohu Wu; Yongquan Zheng (Food Chemistry, 2026)

Oceanographic significance of planktonic foraminiferal assemblages in the northwest Indian Ocean-Basin-Ridge system under monsoon influence - Feng Wang; Yunhai Li; Xuan Ding; Mingjiang Cai; Zhikun Lai; Jian Chen; Pengfei Shen; Liang Wang; Xiang Ye (Journal of Oceanology and Limnology, 2026)

Herbiconiux dendrobii sp. nov., a Novel Bacterium Isolated from Dendrobium devonianum Sawdust Substrate - Hao Liang; Fang Zhao; Hong-Bo Zha; Zhang-Gui Ding; Le-Le Li; Jiang-Yuan Zhao; Zhi-Ran Zhao; Min Zheng; Jian-Sheng Cheng; Hui-Cheng Deng; Shu-Kun Tang; Ming-Gang Li (Current Microbiology, 2026)

Electroplating parks as hidden sources of novel plastic additives: Occurrence, migration pathways, and ecological risks - Zi-Tong Li; Zecong Ding; Yingjie Chen; Kai Cui; Li Wang; Hai-Yan Zhang; Qian Jiang; Li-Qian Lin; Jian-Liang Zhao (Water Research, 2026)

Scour mechanism and efficiency contrast between under-expanded and expanded air jets in underwater - Yaohui Qiang; Yanchong Duan; Liekai Cao; Dejun Zhu; Jian Jiao; Lei Ding; Xiping Dou; Danxun Li (Ocean Engineering, 2026)

Tracing fluid evolution forming multistage wolframite mineralization in vein-type tungsten (-tin) deposit: new insight from LA-ICP-MS analysis of fluid inclusion - Zhi-Lin Cheng; Jun-Yi Pan; Pei Ni; Li-Li Chen; Jian-Ming Cui; Zhe Chi; Jun-Ying Ding (Mineralium Deposita, 2026)

Response of phytoplankton functional groups and biodiversity to seasonal changes in environmental factors in coastal waters - Jian Qi; Xiajie Wang; Lichi Ding; Qinchao Zhang; Jiaxuan Li; Shimin Yang (Ocean & Coastal Management, 2026)

RBOHC-derived ROS control plant nitrate starvation response via WRKYs-activated expression of high-affinity nitrate transporters - Tian Yuan; Meng-Qi Cui; Chen Xu; Jing-Ying Yan; Wo-Na Ding; Ji-Ming Xu; Yun-Rong Wu; Gui-Xin Li; Yu Liu; Dong Zhang; Chuan-Zao Mao; Moussa Benhamed; et al. (Science Bulletin, 2026)

Translocation, metabolism and distribution of multi-pesticides in rats - Kai Cui; Liping Fang; Ruiyan Ding; Wanru Su; Shuai Guan; Jingyun Liang; Teng Li; Junhua Liu; Jian Wang; Zhan Dong; Xiaohu Wu; Yongquan Zheng (Pesticide Biochemistry and Physiology, 2026)

Spatiotemporal evolution of trade-off/synergy relationships and bundles in ecosystem services in Fujian, China: An integrated PLUS-InVEST-SOM framework - Zhihui Lin; Zhu He; Chenjie Ye; Yanan Li; Haolan Liu; Shanshan Ding; Xiaoyang Qiao; Jiayu Xiong; Jiakang Huang; Xisheng Hu; Jian Li (Journal of Cleaner Production, 2026)

DSSAT-PSO coupling-driven intelligent optimization for regional nitrogen management: Sequence module refinement and development - Jian-Ning Liao; Bin Wang; Xiu-Fang Zhang; Qun Wu; Li-Yao Zhou; Yu-Lai Ding (Field Crops Research, 2026)

Wheat seed emergence and grain yield are enhanced by ditch-buried straw return and soil rolling via improving root-soil contact and soil water retention - Xinhu Guo; Yuekai Wang; Tianyu Ding; Yue Zhang; Zhenzhen Li; Yaguang Xue; Yafeng Wei; Jian Liu; Feng-Min Li; Haishui Yang (Field Crops Research, 2026)

Characterization of Neomegalonema-dominated granulation in aerobic granules bioreactor: Evidence for stable filamentous granulation and quorum sensing-related activities - Lili Sun; Hanquan Wen; Lu Ding; Chao Qin; Mingxi Chen; Shike She; Xinchao Zhu; Jian Wang; Zengyang He; Yaping Zhang; Zhiqiang Xu; Quan Shu; et al. (Environmental Research, 2026)

Three-dimensional morphological characterization and quantitative roughness classification of loess joint surfaces - Yanfeng Li; Jian Xu; Mengqi Wang; Liangkun Ding; Yilan He (Engineering Geology, 2026)

Two modes of extreme central Arctic sea ice reduction: temperature advection and sea ice motion dominance - Zhenlin Li; Ruichang Ding; Fei Huang; Jian Shi; Shumeng Zhang (Climate Dynamics, 2026)

COL8A1-positive cancer-associated fibroblasts are drivers of 5-fluorouracil resistance in colorectal cancer - Muzi Ding; Yue Li; Zixuan Liu; Shangshang Hu; Jinwei Lou; Yuhan Chen; Jian Qin; Mu Xu; Huiling Sun; Tao Xu; Shukui Wang; Yuqin Pan (Apoptosis, 2026)

Particle size and chemical constituents of ambient particulate pollution associated with conjunctivitis in southeastern coastal area of China - Liujie Zhu; Tao Zhang; Yingnan Xu; Ying Li; Dongyue Chai; Yanfeng Liao; Zuqiong Song; Jian Wang; Zhen Wang; Wei Shan; Wenhui Liu; Hui Guo; et al. (Air Quality, Atmosphere & Health, 2026)

Unique ecological functions of viral communities potentially influence microbial adaptability in deep-sea ferromanganese nodule deposits - Yu-Kang Li; Ge-Yi Fu; Zhen Rong; Jun-Qing Chen; Zhi-Hao Ding; Zu-Xin Zhang; Hua-Hua Jian; Wen-Sheng Shu; Yue-Hong Wu; Xue-Wei Xu (Journal of Hazardous Materials, 2026)

Ti(IV)-incorporated covalent organic frameworks for efficient dark-photocatalytic reduction of U(VI) - Li-Ling Chen; Cheng-Peng Niu; Rui Zhang; Yun-Peng Wu; Zhen-Wen Zhang; Bin Lin; Cheng-Rong Zhang; Li Zhang; Ru-Ping Liang; Jian-Ding Qiu (Journal of Environmental Chemical Engineering, 2026)

Synergistic effect between biochar and nanoscale zero valent iron effectively mitigated nitrous oxide emissions from a flooded paddy soil - Mingjun Ding; Yu Zhou; Zhe Li; Jian Zhang (Journal of Environmental Chemical Engineering, 2026)

Interface gap reduction and its mechanistic origins in stirrup-confined CFST columns - Faxing Ding; Jie Wu; Fei Lyu; Liping Wang; Hao Sun; Jian Li; Jinxian He; Yueshou Zhao; Mingwen Hu; Yu Mei; Zhiqiang Chen; Weiyao Tang; et al. (Engineering Structures, 2026)

Metallic-phase MoS2 nanosheets boost polysulfide redox kinetics to high-performance polysulfide-based flow batteries - Ruiyu Liu; Su Yan; Xin Huang; Weizhe Xiang; Jian Xu; Zhizhao Xu; Mei Ding; Binglei Liu; Hongtai Li; Xiaolei Huang; Shengqi Chu; Guangmin Zhou; et al. (Chemical Engineering Journal, 2026)

A highly efficient nanocopper hydroxide activates plant immune resistance and confers tolerance to salt and drought stress in rice - Chongchong Lu; Zimeng Li; Taizhong Huang; Muhammad Zunair Latif; Haifeng Liu; Mingxia Hao; Yanke Jiang; Yingzhe Yue; Jian Zhang; Miaomiao Deng; Qian Du; Sifan Yang; et al. (Chemical Engineering Journal, 2026)

Hydroxybutyl chitosan-based thermosensitive hydrogel enhanced osteoporotic bone regeneration through sustained release of alendronate and BMP-2 - Mingyuan Lei; Haibing Liu; Qiang Zhong; Libo Zhao; Jingwen Liu; Huaming Mai; Yuheng Zhang; Hongyu Wang; Yourong Chen; Rong Chen; Yixin Xu; Hao Li; et al. (Carbohydrate Polymers, 2026)

Plasma MicroRNA and Protein Signature Associated with Obesity in the Chinese Han Population Using MicroRNA Omics and Proteomics Analysis of 1026 Subjects - Yun-Xia Xie; Jian-Ge Qiu; Zhao-Hui Yang; Chen Ding; Le-Ming Shi; Si-Jia Wang; Li Jin; Bing-Hua Jiang (Phenomics, 2026)

Phyllosphere to soil: How long-term fencing reshapes grassland microbial community construction and the functional genes - Jian Li; Yu Zhu; Daniel F. Petticord; David W. Frey; Lijie Huang; Ming-Kang Jin; Michiel Op de Beeck; Quan-Hui Ma; Shu-Huan Jin; Hong Ying; Xi-Mei Xue; Ling Wang; et al. (Agriculture, Ecosystems & Environment, 2026)

Verbascoside from Callicarpa nudiflora Hook extends lifespan in Caenorhabditis elegans via SKN-1 pathway activation - Yuhang Liu; Jiale Wu; Zhiyang Ding; Liru Chen; Manyu Liu; Baoli Li; Xiaokang Li; Jian Li; Wenwen Liu (Biogerontology, 2026)

Gonadal temperature-sensitive gene identification in gynogenetic gibel carp (Carassius gibelio) with temperature-dependent sex determination - Wen-Xuan Du; Zhi Li; Tao Wang; Miao Ding; Ming-Tao Wang; Chun Miao; Xiao-Juan Zhang; Yang Wang; Zhong-Wei Wang; Li Zhou; Jian-Fang Gui; Xi-Yin Li (Aquaculture, 2026)

Deep reinforcement learning framework for the underground mine short-term production scheduling problem - Ning Li; Yi Ding; Bibo Dai; Liguan Wang; Jian Chang; Haiwang Ye; Qizhou Wang (Swarm and Evolutionary Computation, 2026)

amh alleles on XY sex chromosomes regulate male differentiation in amphidiploid Carassius auratus - Chun Miao; Meng Lu; Miao Ding; Ming-Tao Wang; Zhi Li; Tian-Zi Yao; Zhi-Xuan Zhu; Wen-Xuan Du; Jun-Sheng Niu; Xiao-Juan Zhang; Shun Li; Peng Yu; et al. (Science China Life Sciences, 2026)

Microglial Activation Mediates Drp1-Dependent Mitochondrial Fission and Neuronal Apoptosis in a Lipopolysaccharide-Induced Model of Cognitive Dysfunction - Meng-Jie Chen; Jia-Qi Ning; Jia-Xi Liu; Jian-Sheng Luo; Ru-Yu Yan; Yu-Xuan Yang; Xiang Li; Ling-Ling Ding (Molecular Neurobiology, 2026)

Alleviating drought and heat stress: a root-canopy coordination irrigation strategy synergistically elevating grapevine yield, quality, and water productivity - Yudong Chen; Jinliang Chen; Jian Kang; Taisheng Du; Risheng Ding; Zhanwu Dai; Junhua Kong; Zhijie Li; Shaozhong Kang (Agricultural and Forest Meteorology, 2026)

Characteristics and controlling factors of stable isotopes in precipitation based on 9-year monitoring data in the monsoon transition zone of the Tibetan Plateau - Wang Shao-yong; Wang Qiao-li; Kang Shi-chang; Ding Yong-jian; Xue Yu-ang; He Xiao-bo (Agricultural and Forest Meteorology, 2026)

Exploring the role of surface micro-topography in governing dissolved nitrogen dynamics in agricultural runoff during rainfall - Qingwei Zhang; Hao Wang; Fengbao Zhang; Guo Chen; Yuanbi Yi; Yu Pang; Jian Wang; Ding He; Ming Li (Water Research, 2025)

A plasma membrane receptor complex mediates early heat-responsive signaling to trigger nuclear transcriptomic reprogramming in Arabidopsis - Jing Li; Shifeng Wu; Kun Wang; Yang Xu; Xiaoyan Zhang; Xinru Li; Wen Song; Jian-Min Zhou; Zhizhong Gong; Shuhua Yang; Yanglin Ding (Molecular Plant, 2025)

Recognition of a phytocytokine by the DEPR1–SERK2 receptor complex confers multi-pathogen resistance in wheat - Lijun Wang; Jun Zhao; Chuanchun Yin; Hongxu Li; Yanan Xiao; Cuicui Du; Zhaoxi Lu; Yongjian Zhang; Fangshuai Jia; Jiaxin Hao; Jinghui Yan; Yi Zhang; et al. (Molecular Plant, 2025)

PM2.5-bound metallic elements in village and urban airs in North China during wintertime: Concentration, morphology, mixing state, and size distribution - Yinxiao Zhang; Jian Zhang; Xiaotong Jiang; Yuanyuan Wang; Xiaokun Ding; Weijun Li (Journal of Environmental Sciences, 2025)

Enhanced non-enzymatic glucose sensing and underlying kinetics mechanism for nickel cobalt oxide - Jinping Huang; Jun Ding; Jianmei Xu; Tiancheng He; Wenhao Li; Zhihong Yang; Wei Zhou; Jian Sun (Chemical Engineering Journal, 2025)

Multiscale interface engineering via femtosecond laser synergized with micro-Ag interlayer for robust ceramic-metal sintered-joining in protonic ceramic fuel cells - Naiqiang Wang; Xiaoqing Si; Hanyue Ding; Zhihu Zhang; Jianwei Gao; Shaletanati Ake; Xuexue Li; Chun Li; Junlei Qi; Jian Cao (Chemical Engineering Journal, 2025)

Decades’ progress and prospects on maize functional genomics and molecular breeding - Qing Li; Jinsheng Lai; Jian Chen; Lin Li; Weibin Song; Beibei Xin; Hainan Zhao; Yingjie Xiao; Feng Tian; Gang Li; Yameng Liang; Lei Liu; et al. (Science China Life Sciences, 2025)

ERO1A-positive tumor epithelial cells in colorectal cancer progression: a multi-omics perspective - Shangshang Hu; Jinwei Lou; Yuhan Chen; Muzi Ding; Jian Qin; Junjie Nie; Yue Li; Zixuan Liu; Mu Xu; Huiling Sun; Qianni Xiao; Yuqin Pan; et al. (Apoptosis, 2025)

The response characteristics of fault-crossing tunnel subjected to different sequential combination actions of strike-slip fault dislocation and seismic wave propagation - Xiancheng Mei; Changdong Ding; Jianhe Li; Bo Lou; Zhen Cui; Mingnan Xu; Qian Sheng; Yajie Song; Jian Chen (Soil Dynamics and Earthquake Engineering, 2025)

Promoting acetate production on the in situ reconstructed Cu nanoislands via pressure-regulated CO adsorption and electroreduction - Rongxing Qiu; Jiaran Li; Jiafeng Du; Siwang Zhang; Lingzhi Ding; Jinlong Wan; Cheng Li; Jinyu Ye; Jin-Chao Dong; Yuanjie Pang; Jian-Feng Li; Shuliang Yang; et al. (Science Bulletin, 2025)

Residue behavior, processing factors and risk assessment of four new fungicides in grapes from field to processing - Kai Cui; Shuai Guan; Jingyun Liang; Rui Ni; Ruiyan Ding; Teng Li; Jian Wang; Junhua Liu; Liping Fang; Zhan Dong; Xiaohu Wu; Yongquan Zheng (Food Control, 2025)

Chronic DBP exposure may cause reduced fertility in female mice by interfering with the HPO axis - Chao Yan; Min Wu; Haiyan Peng; Jian Wan; Ren Li; Xin Ye; Hongmao Zhang; Shumao Ding (Environmental Pollution, 2025)

Sugar-based block copolymer/carbon nanotube nanocomposites for thermoelectric applications - Yen-Yu Chen; Hong Li; Chih-Jung Lin; Koshin Tanaka; Meng-Hao Lin; Shao-Huan Hong; Min-Chi Fu; Jian-Fa Ding; Yu-Jane Sheng; Redouane Borsali; Tsuyohiko Fujigaya; Cheng-Liang Liu (Chemical Engineering Journal, 2025)

Electrolyte design for highly reversible zinc anodes via prismatic plane growth and nucleation kinetics regulation - Mingyu Shao; Xinrui Ma; Yiming Jiang; Yu Tian; Wenquan Ding; Jin Liu; Feng Qiao; Junyu Zhu; Yaning Li; Xiaocun Liu; Jian Liu; Bo Li; et al. (Chemical Engineering Journal, 2025)

Ethylene-responsive factor HvERF72 regulates starch synthesis and B-type starch granules initiation in barley - Gaozong Zhou; Jinjin Ding; Yulong Li; Qiang Xu; Yazhou Zhang; Huaping Tang; Pengfei Qi; Mei Deng; Jian Ma; Guoyue Chen; Jirui Wang; Na Lin; et al. (Carbohydrate Polymers, 2025)

SsGSDMEa-mediated pyroptosis is involved in Photobacterium damselae subsp. piscicida infection in the black rockfish Sebastes schlegelii - Xin Ding; Yuan Chen; Zihao Yuan; Jian Zhang; Xuepeng Li; Hang Xu; Li Sun (Aquaculture, 2025)

Unraveling the links between molecular weight and multidimensional dynamics of dissolved organic matter in the runoff from gentle sloping land under rainfall - Guo Chen; Hao Wang; Qiang Zhang; Chao Chang; Fei Wang; Qingwei Zhang; Jian Wang; Yu Pang; Ming Li; Biao Zhu; Ding He (Water Research, 2025)

HySwinFormer: A hybrid deep learning architecture for fine-grained classification of marine microalgae - Jiaxuan Li; Min Fu; Lichi Ding; Jian Qi; Jingqiang Yang; Shimin Yang (Science of The Total Environment, 2025)

Controlled release of bittern-loaded water-in-water emulsion as a novel strategy to regulate the gelation properties of tofu - Shuhan Shen; Jiaqi Yang; Fan Wu; Zixuan Wang; Jiaqiang Chen; Ziqian Li; Yong Fang; Xiaoyi Jiang; Jian Ding (Food Research International, 2025)

Targeting superfast sodium energy of coal-based hard carbon by precise regulation of pseudographitic structure - Yaxin Huang; Zhidong Hou; Jianfang Wang; Yongli Li; Ting Ma; Ying Zhan; Chunguang Wei; Jian-Gan Wang; Ding Nan (Chemical Engineering Journal, 2025)

Rational design of freeze-crosslinked polysaccharide sponges for efficient non-compressible hemostasis and liver repair - Peng Zhou; Weixiao Ding; Hongyan Wang; Xinmeng Li; Jian Cui; Guangjiu Liu; Zhiqi Chen; Chao Tang; Yishan Jiang; Lei Zhang; Dongping Sun (Carbohydrate Polymers, 2025)

Organic nitrates in coastal aerosols: Seasonal dynamics, influencing factors, and formation pathways - Mengke Tian; Zhijian Ding; Jia Chen; Juntao Huo; Guochen Wang; Jian Xu; Hao Li; Ziwei Liu; Yunkai Wang; Nan Ye; Xiaofei Qin; Yanfen Lin; et al. (Atmospheric Environment, 2025)

Characteristics and mechanisms of summer long-lived heatwaves in Western North America: Perspective from Rossby wave train - Qian Qiang; Jian Shi; Jiajie Chen; Hengxing Qu; Yichuan Lu; Fei Huang; Chun Li; Saisai Ding (Atmospheric Research, 2025)

Genomic characterization of Gillisia xinjiangensis sp. nov.: insights into nitrogen metabolism, stress adaptation, and application potential - Hao-hao Wang; Chi Zhang; Ya-qin Chen; Yi-fan Guo; Li-jian Ding; Sheng-fa Zhang; Gai-jun Du; Wei-yan Zhang; Shan He (Systematic and Applied Microbiology, 2025)

Soil respiration and carbon sequestration response to short-term fertilization in wheat-maize cropping system in the North China Plain - Jian Zhang; Peikun Li; Lin Li; Mina Zhao; Peisen Yan; Yuan Liu; Wei Li; Shengyan Ding; Qinghe Zhao (Soil and Tillage Research, 2025)

Identification of heavy metal transport-related genes and microRNAs in response to cadmium toxicity and micronutrient deficiency in barley roots - Liuhui Kuang; Jian Chen; Jie Ding; Tao Yan; Fei Gao; Lin Li; Zhigang Han; Dezhi Wu (Journal of Hazardous Materials, 2025)

MICP-enhanced wind erosion resistance of desert sand: process parameter optimization and microstructural mechanism - Jian Xu; Liangkun Ding; Zihan Li; Jiayuan Li (Geomechanics for Energy and the Environment, 2025)

Dissipation and metabolism of fluxapyroxad, oxathiapiprolin and penthiopyrad in grapes: A comprehensive risk assessment from field to raisins - Kai Cui; Liping Fang; Ruiyan Ding; Rui Ni; Jingyun Liang; Teng Li; Jian Wang; Junhua Liu; Shuai Guan; Zhan Dong; Xiaohu Wu; Yongquan Zheng (Food Chemistry, 2025)

The research progress of Ganoderma as a medicinal and edible product - Meilin Wang; Ding Li; Xu Gao; Xinze Wang; Li Zhang; Jiaxin Ding; Ke'er Xuan; Ge Wang; Yan Bai; Jian Gong (Food Bioscience, 2025)

Constructing nitrogen-doped porous organic polymer- supported single-atom cobalt catalysts for highly efficient hydroformylation of internal olefins - Yuqing Wang; Miao Jiang; Na Liu; Tian Tian; Changdao Li; Zhao Sun; Gewen Yu; Yanming Wang; Wenxiu He; Jian Ding; Li Yan; Yunjie Ding (Chemical Engineering Journal, 2025)

A Seismic Multi-Attribute Sandbody Identification Method Based on the LightGBM-RFECV Coupling Algorithm - Teng-fei Ren; Zhi-bing Feng; Ying Zhang; Xiang Zhang; Li Jiang; Yuan-li Ning; Jing-yi Wang; Jian Ding; Zeng-shuo Qi (Applied Geophysics, 2025)

Forecasting Ocean Mesoscale Eddies in the Northwest Pacific in a Dynamic Ocean Forecast System - Jiakang Zhang; Hailong Liu; Mengrong Ding; Yao Meng; Weipeng Zheng; Pengfei Lin; Zipeng Yu; Yiwen Li; Pengfei Wang; Jian Chen (Journal of Marine Science and Engineering, 2025)
The LICOM Forecast System (LFS), a global eddy-resolving ocean forecasting system, provides 1–15-day forecasts of ocean mesoscale eddies (OMEs). This study conducts a comparative analysis of the forecast results against observational data, thereby evaluating the performance of the LFS. Results show that LFS underestimates the number of eddies by ~10% and their amplitude by ~30%, while overestimating eddy radius by ~5% and velocity by ~25%. Forecasted eddies are matched on a one-to-one basis with observed eddies based on distance, ensuring that those forecasted eddies that can locate corresponding counterparts in the observational dataset yield accurate forecasts. The outcomes reveal that the LFS successfully forecasts 63% of the eddies in the NWP. The characteristics of these accurately forecasted eddies are delineated. The findings indicate that eddies with greater amplitudes are more likely to be accurately predicted. Additionally, we further scrutinized the correlation between eddy attributes and forecast performance, revealing that with an increase in amplitude or a decrease in velocity, the LFS produces forecasts with improved locational accuracy. The mean forecast error in eddy position is 79.94 km for a 1-day lead time, which decreases to 70.97 km for eddies with amplitudes exceeding 1 cm and velocities below 1 km/day.

Observation of anti-Klein tunneling of chiral phonons - Hongzhu Li; Yang Liu; Qian Ding; Tianzhi Yang; Chenglin Han; Mengxin He; Jian-Hua Jiang; Ying Li (Science Bulletin, 2025)

The regulatory module involved in ABA-induced ethylene production and fruit ripening in banana and its implications - Liming Zeng; Zhengnan Xie; Zehong Ding; Yan Yan; Jinghao Yang; Weiwei Tie; Guangyuan He; Guangxiao Yang; Jian Zeng; Yin Li; Meiying Li; Wei Hu (Postharvest Biology and Technology, 2025)

A symbiotic bacterium regulates the detoxification metabolism of deltamethrin in Aedes albopictus - Si-jia Deng; Lei Tu; Lin Li; Ju-ping Hu; Ju-lin Li; Jian-xia Tang; Mei-chun Zhang; Guo-ding Zhu; Jun Cao (Pesticide Biochemistry and Physiology, 2025)

Insights into the synergistic mechanisms of citric acid in detoxifying cadmium in tall fescue - Jian Cui; Wenqi Ding; Shuning Li; Xuanyang Wu; Jianing Wang; Qiuyu Su; Junxiang Qi; Xiaoyang Sun; Jinmin Fu (Journal of Hazardous Materials, 2025)

Effects of high-concentration sulfamethoxazole on antibiotic resistance genes during swine manure aerobic composting - Shuangshuang Ma; Li Wang; Jingtao Ding; Haibin Zhou; Yujun Shen; Jian Wang; Yanxin Chen; Yan Yang (Journal of Environmental Chemical Engineering, 2025)

Adsorption of dibutyl phthalate by multi-walled carbon nanotubes aggravates hemogram, liver and kidney damage in rats - Min Wu; Chao Yan; Haiyan Peng; Jian Wan; Ren Li; Xin Ye; Hongmao Zhang; Shumao Ding (Food and Chemical Toxicology, 2025)

An efficient and precise (micro)plastic identification method: feature infrared spectra extraction based on EIS-VIP-CARS and ANN modeling - Shuangsheng Zhang; Jing Qiang; Hanhu Liu; Junjie Zhou; Jun Li; Jian Chen; Qiang Ding; Kuimei Qian (Environmental Research, 2025)

Resolving the Snowball Earth conundrum: the role of marine dissolved organic carbon pool - Bing Shen; Xianguo Lang; Ruimin Wang; Yonggang Liu; Shihong Zhang; Tianzheng Huang; Xuelei Chu; Yixin Cui; Weiming Ding; Yuansheng Du; Ran He; Kangjun Huang; et al. (Science Bulletin, 2025)

Development of chitosan-carboxymethyl cellulose edible films loaded with blackberry anthocyanins and tea polyphenols and their application in beef preservation - Han Chen; Xiuhua Meng; Fang Zhang; Jian Chen; Xiaoqin Ding; Tunyu Jian; Guanting Niu; Bei Tong; Yanan Gai; Huifang Zhao; Weilin Li; Han Lü (Food Hydrocolloids, 2025)

Calcium phytate cross-linked polysaccharide hydrogels for selective removal of U(VI) from tailings wastewater - Lan Lei; Rui Zhang; Rui-Xiang Bi; Zhi-Hai Peng; Xin Liu; Tie-Ying Shi; Li Zhang; Ru-Ping Liang; Jian-Ding Qiu (Water Research, 2025)

Application of computer vision techniques to fermented foods: An overview - Zheli Song; Yuanbo Li; Hongyuan Zhao; Xiaogang Liu; Hailong Ding; Qiansu Ding; Dongna Ma; Shuangping Liu; Jian Mao (Trends in Food Science & Technology, 2025)

Effects of combined continuous renal replacement therapy and ulinastatin on cytokine levels and clinical outcomes in patients with sepsis - Anwaier Apizi; Jian Li; Wei Liu; Liangjie Dong; Yunfei Ding; Zhaoxia Yu (Toxicology and Applied Pharmacology, 2025)

Knockdown of Mageb16 disrupts cell proliferation and lineage specification during mouse preimplantation development - Xiaoqing Wu; Xin Ming; Qing Liu; Ruisong Bai; Xiaoyu Zhang; Yuheng Bi; Qing Ding; Shangrong Zhang; Jian Li; Hongcheng Wang; Yong Liu (Theriogenology, 2025)

GAIN: A long-term maize germplasm innovation plan - Yang Wang; Peng Zhang; Yingjie Xiao; Hai-Jun Liu; Junqiang Ding; Yanzhi Qu; Jionghao Gao; Wenlong Li; Xiangyang Guo; Angui Wang; Wenqiang Li; Gengshen Chen; et al. (Molecular Plant, 2025)

The recruitment of alkaline phosphatase-positive endogenous neural stem cells enables robust neurogenesis and neural pathways reconstruction following spinal cord injury - Rong-Jie Wu; Jia-Lin Liu; Zheng-Hong Chen; Jing Xu; Ying Ding; Hai-Yang Yu; Chuang-Ran Wu; Shang-Bin Yang; Rui Liu; Yi-Nan Guo; Yue Yang; Ting-Ting Wu; et al. (Chemical Engineering Journal, 2025)

Epigenetics in the modern era of crop improvements - Yan Xue; Xiaofeng Cao; Xiangsong Chen; Xian Deng; Xing Wang Deng; Yong Ding; Aiwu Dong; Cheng-Guo Duan; Xiaofeng Fang; Lei Gong; Zhizhong Gong; Xiaofeng Gu; et al. (Science China Life Sciences, 2025)
Epigenetic mechanisms are integral to plant growth, development, and adaptation to environmental stimuli. Over the past two decades, our comprehension of these complex regulatory processes has expanded remarkably, producing a substantial body of knowledge on both locus-specific mechanisms and genome-wide regulatory patterns. Studies initially grounded in the model plant Arabidopsis have been broadened to encompass a diverse array of crop species, revealing the multifaceted roles of epigenetics in physiological and agronomic traits. With recent technological advancements, epigenetic regulations at the single-cell level and at the large-scale population level are emerging as new focuses. This review offers an in-depth synthesis of the diverse epigenetic regulations, detailing the catalytic machinery and regulatory functions. It delves into the intricate interplay among various epigenetic elements and their collective influence on the modulation of crop traits. Furthermore, it examines recent breakthroughs in technologies for epigenetic modifications and their integration into strategies for crop improvement. The review underscores the transformative potential of epigenetic strategies in bolstering crop performance, advocating for the development of efficient tools to fully exploit the agricultural benefits of epigenetic insights.

Investigation of brittle characteristics and hydraulic fracture propagation in deep sandstone reservoirs in the central Junggar Basin - Lianchong Li; Jian Lu; Wenqiang Mu; Ran Ding; Anhai Zhong; Feng Yang; Mingyang Zhai (Bulletin of Engineering Geology and the Environment, 2025)

The sedimentological heterogeneities and responses to controlling factors in Toutunhe Formation of Xiayan Rise, Junggar Basin - Nai-xiang He; Xiang Li; Ya-jie Ding; Rui Qi; Gang Xu; Zi-jian Han; Chao Hou; Lei Xie (Applied Geophysics, 2025)

Study on automatic berthing of large under-actuated vessel with multi-tug collaboration - Guoquan Chen; Chong Ding; Jian Yin; Hong Zhu; Yuqin Li (Ocean Engineering, 2025)

Revealing the enhanced role of hydroxylamine and bimetals in the CuFe2O4/PMS/HA system towards effective degradation of organic contaminants - Yulong Li; Jiayi Ren; Jing Ding; Yongxin Wang; Hui Yan; Fengyang Liu; Jian Wei; Xuedong Zhai; Abdulaziz Al-Anazi; Polycarpos Falaras (Journal of Hazardous Materials, 2025)

Multi-frequency tomographic SAR: A novel 3-D imaging configuration for limited acquisitions - Jian Zhao; Zegang Ding; Zhen Wang; Tao Sun; Kaiwen Zhu; Yuhan Wang; Zehua Dong; Linghao Li; Han Li (ISPRS Journal of Photogrammetry and Remote Sensing, 2025)

Multiomics analysis revealed the effects of polystyrene nanoplastics at different environmentally relevant concentrations on intestinal homeostasis - Jian-Zheng Yang; Ji-Hui Li; Jia-Li Liu; An-Ding Zhou; Hui Wang; Xiao-Li Xie; Kai-Kai Zhang; Qi Wang (Environmental Pollution, 2025)

Curculigoside exhibits multiple therapeutic efﬁcacy to induce apoptosis and ferroptosis in osteosarcoma via modulation of ROS and tumor microenvironment - Ziyang Ma; Yirong Wang; Xiaoyu Zhang; Shi Ding; Jian Fan; Tian Li; Xin Xiao; Jing Li (Tissue and Cell, 2025)

Metallization-mediated charge transfer in cocrystals for efficient photocatalytic decontamination of mustard-gas simulant - Li Zhang; Xiao-Lin Liu; Chen Sun; Yu-Ting Luo; Qiang Shi; Ru-Ping Liang; Jian-Ding Qiu (Journal of Environmental Chemical Engineering, 2025)

Biomass moulding fuel for zero-emission agricultural waste management: A case study of tobacco curing in China - Tianbao Ren; Ding Yan; Youjian Zhang; Xiaolong Li; Jian Chen; Chuliang Wang; Chi Wang; Peiyan Li; Longfei Wang; Qiang Zeng; Xianjie Cai (Journal of Environmental Management, 2025)

Effects of salt ions and pH on deamidated soybean protein hydrogels formation: Molecular structure, thermal aggregation and network - Tang-Hao Li; Yao-Qin Yang; Gao-Shang Wang; Ding-Yang Lv; Jian Guo; Zhi-Li Wan; Xiao-Quan Yang (Food Chemistry, 2025)

Glutinous rice gel as all-natural ink supply for extrusion-based food 3D printing – the chemical basis of gel printability - Xiaoyi Jiang; Wei Dai; Qu Yan; Di Chen; Zhihai Li; Xinyang Sun; Jian Ding; Ziqian Li; Yong Fang (Food Chemistry, 2025)

Inhibition of platelet activation process upon tris (2-chloroethyl) phosphate exposure: Role of PFKP-mediated glycolysis and the pentose phosphate pathway - Ziyuan Li; Pu Chen; Yongfeng Lin; Jingxu Zhang; Jian Ding; Rifat Zubair Ahmed; Xiaoting Jin; Yuxin Zheng (Environmental Pollution, 2025)

Enhanced removal of cadmium from aqueous environments and soil during electrokinetic remediation using Si-Mg modified sawdust-based biochar as an adsorbent and permeable reactive barrier material - Jian Tian; Xianzhen Li; Wei Ding; Kewei Shuai; Qing Zhen; Diao She (Chemical Engineering Journal, 2025)

Overcoming the conventional thermodynamic limit of water electrolysis to boost renewable energy storage - Hui Sun; Wen-Tao Bi; Qian He; Li Zhu; Yu-Qing Dong; Fang Li; Zhen-Guo Guo; Jun Ding; Jian-Bo He (Chemical Engineering Journal, 2025)

Uncovering the charge storage mechanism of anti-perovskite nitrides Co3InN cathode materials in alkaline aqueous electrolytes - Yuming He; Rui Ding; Yi Li; Jian Guo; Yiqing Lu; Ziyang Yan; Zhiqiang Chen; Jiajie Luo (Chemical Engineering Journal, 2025)

Evaluation of Immunoregulatory Functions of a Peptide From Rice: An in Silico and in Vitro Study - Ying Wu; Zhimeng Zhang; Zhimin Zhang; Tingmin Qu; Shiyu Wen; Hao Wu; Mao-Long Chen; Li Ding; Yufei Xie; Qingming Huang; Jian Hu; Li Wen (International Journal of Peptide Research and Therapeutics, 2025)

Dynamic analysis of intrahepatic T cells reveals a unique group of restorative Cxcr3+ tissue-resident CD4 T cells in acute liver injury - Shen-Xi Ouyang; Yong-Gang Xu; Peng Ding; Yue Long; Zhen Zhang; Si-Jia Sun; Yan Zhang; Hang Yin; Jia-Bao Zhang; Qi Cao; Fu-Ming Shen; Pei Wang; et al. (Toxicology, 2025)

Optical and molecular techniques are complementary to understand the characteristics of dissolved organic matter in the runoff from sloping croplands with various micro-topographies during rainfall - Guo Chen; Qing-wei Zhang; Hao Wang; Ren Geng; Jian Wang; Yuan-bi Yi; Ming Li; Ding He (Journal of Hydrology, 2025)

Electronic engineering induced ultrafine non-noble nanoparticles for high-performance hydrogen evolution from ammonia borane hydrolysis - Siyuan Tang; Linlin Xu; Xiang Ding; Quanjiang Lv; Haotian Qin; Aosong Li; Xinchun Yang; Jian Han; Fuzhan Song (Fuel, 2025)

Self-assembled preparation of wheat germ gliadin and (−)-epigallo-catechin 3-gallate nanoparticles: Structural characterization, formation mechanism and bioactivity - Zhi-Tong Zhu; Zhi-Rui Ding; Yu-Qing Liu; Ying Zhang; Jian-Zheng Li; Si-Yi Han; Xian-Ming Liu; Ming Hui; Na Liu; Ai-Mei Liao (Food Bioscience, 2025)

Activated CdS/ sulfur doped g-C3N4 photocatalyst for dye and antibiotic degradation: Experimental and DFT verification of S-scheme heterojunction - Xu Duan; Jian Yang; Jiaqing Zhu; Hongbin Li; Yujie Fang; Runxue Liu; Chen Yang; Weizao Liu; Chunlian Ding; Qingcai Liu; Jiangling Li; Shan Ren (Environmental Research, 2025)

Anti-Müllerian hormone deficiency leads to two distinct ovarian phenotypes with different alterations of sex hormones in gynogenetic carp - Chun Miao; Zhi Li; Tian-Zi Yao; Ming-Tao Wang; Miao Ding; Xiao-Juan Zhang; Yang Wang; Zhong-Wei Wang; Li Zhou; Jian-Fang Gui; Xi-Yin Li (Aquaculture, 2025)

Effect of crowding stress on liver health, gut permeability and gut microbiota of genetically improved farmed tilapia (GIFT, Oreochromis niloticus) - Jian Zhang; Jie Chen; Hui Liang; Ming Li; Wenhao Zhou; Yalin Yang; Zhen Zhang; Qianwen Ding; Chao Ran; Zhigang Zhou (Aquaculture, 2025)

Sophflarines B−E, four distinctive matrine alkaloids from Sophora flavescens with potential neuroprotective activities - Ding Luo; Qian Xie; He Tian; Xin-Kai Zheng; Jia-Wen Zou; Yue-Hao Huang; Yan-Jun Chen; Chun-Lin Fan; Li-Jun Hu; Jian-Xin Chen; Hao Wang; Guo-Cai Wang; et al. (Phytochemistry, 2025)

Prediction of hydrate formation boundaries in pure water and salt/alcohol containing systems based on prior knowledge and artificial intelligence - Shu-Kai Chen; Xiao-Fang Lv; Jian-Ping Ding; Yang Liu; Ji-Miao Duan; Hui Du; Chuan-Shuo Wang; Ming-Guo Peng; Qian-Li Ma; Shi-dong Zhou (Fuel, 2025)

Doping induced diatomic active sites over MoO3-x for efficient and stable photocatalytic N2 reduction to ammonia - Xinru Yu; Yongchao Wang; Jian Ding; Zhen Li; Bing He; Zhaowu Zeng; Panxing Zhu; Xiangran Xu; Xiaoyi Liu; Huan Wang; Yang Wang (Chemical Engineering Journal, 2025)

PbI2 intercalation and residual elimination strategy for sequential inverted perovskite solar cells - Zhuowei Du; Zhu Ma; Tangjie Yu; Zhangfeng Huang; Shanyue Hou; Qianyu Liu; Yanlin Li; Yi Chen; Qiang Yang; Wei You; Junbo Yang; Hao Du; et al. (Chemical Engineering Journal, 2025)

Associations of Urinary Nickel with NAFLD and Liver Fibrosis in the USA: A Nationwide Cross‑Sectional Study - Kening Zhang; Chunxiao Yang; Xue Zhao; Yuanyuan Wang; Zhuo Gu; Ruiming Yang; Haiyan Ding; Shuangshuang Li; Jian Qin; Xia Chu (Biological Trace Element Research, 2025)

Effects of nitrite exposure on the oxidative stress, immune response and intestine microbiota of Procambarus clarkii - Dan-Dan Bian; Yan-Xia Shi; Xi-Rong Zhu; Xiao-Li Sun; Xuan Xu; Lu Ding; Dai-Zhen Zhang; Qiu-Ning Liu; Bo-Ping Tang; Bao-Jian Zhu (Aquaculture, 2024)

Fluid inclusion LA-ICP-MS constraint on hydrothermal evolution of proximal cassiterite-bearing quartz veins in the giant Gejiu orefield: Implications for controls on metallogenic potential of granite-related skarn system - Zhi-Lin Cheng; Pei Ni; Jun-Yi Pan; Liang Han; Wen-Sheng Li; Stefano Albanese; Zhe Chi; Jun-Ying Ding; Jian-Ming Cui (Journal of Geochemical Exploration, 2024)

Chain effect of Mn4+/ Mn3+ and OLattice on La1-xSrxMnO3 catalysts for lower thermally driven CO oxidation - Xu Duan; Jian Yang; Jiaqing Zhu; Hongbin Li; Huan Li; Runxue Liu; Yujie Fang; Qingcai Liu; Weizao Liu; Chunlian Ding; Jiangling Li; Shan Ren (Journal of Environmental Chemical Engineering, 2024)

CCL2-scavenging nanodecoy hydrogel multi-step remodel monocytes recruitment and macrophages polarization for periodontitis treatment - Yuxiao Wang; Guichun Wang; Jiaxin Li; Maomao Tang; Baoqing Jia; Zixuan Shu; Yang Ding; Chengjun Peng; Shuangying Gui; Jian Guo (Chemical Engineering Journal, 2024)

Lattice energy transfer from homo-crystalline substitution for enhanced piezo-photocatalytic CO2 conversion - Chuanzhou Bi; Hangmin Xu; Ganghua Zhou; Hao Song; Jian Xu; Qijun Li; Bin Wang; Penghui Ding; Lvzhou Li; Paul K. Chu; Hui Xu; Xingwang Zhu; et al. (Chemical Engineering Journal, 2024)

Molecular phylogeny of Podoscypha (Basidiomycota, Podoscyphaceae) with descriptions of four new species, inferred from nuclear rDNA sequences - Fu-Chang Huang; Jian-Tian Lin; Hai-Fu Zheng; Yun-Long Liang; Miao-Miao Li; Cheng-Pei Ding (Mycological Progress, 2024)

Comprehensive Analysis of the SUMO-related Signature: Implication for Diagnosis, Prognosis, and Immune Therapeutic Approaches in Cervical Cancer - Xing Zhang; Jian Cao; Xiuting Li; Yan Zhang; Wenjing Yan; Bo Ding; Jing Hu; Haohan Liu; Xue Chen; Yamei Nie; Fengying Liu; Ning Lin; et al. (Biochemical Genetics, 2024)

Solibacillus ferritrahens sp. nov., a novel siderophore-producing bacterium isolated from Wumeng Mountain National Nature Reserve in Yunnan Province - Xiao-Di Liu; Jiang-Yuan Zhao; Le-Le Li; Jian-Yu Li; Pei-Wen Yang; Song-Guo Liang; Lu-Yao Feng; Zhu-Feng Shi; Zhang-Gui Ding; Ming-Gang Li; Shu-Kun Tang (Antonie van Leeuwenhoek, 2024)

Global Meta‐Analysis of Individual and Combined Nitrogen Inhibitors: Enhancing Plant Productivity and Reducing Environmental Losses - Wenyu Wang; Yaqun Li; Wei Wang; Keren Ding; Kun Zhang; Yulan Zhang; Kai Liu; Jingyuan Li; Dongwei Li; Ruiyuan Lian; Daijia Li; Jian Gu; et al. (Global Change Biology, 2024)
Nitrogen (N) transformation inhibitors have been widely recognized as a promising strategy to enhance crop productivity and mitigate N losses. However, the effectiveness of individual or combined inhibitors can vary significantly across different agroecosystems. Using meta‐analysis and cost–benefit analysis (CBA), we synthesized findings from 41 peer‐reviewed studies (285 observations) globally to evaluate the efficacy of urease inhibitors (UIs), nitrification inhibitors (NIs), and combined inhibitors (UINIs). We assessed their influence on soil inorganic N transformations, greenhouse gas emissions, and crop productivity across diverse climates, soil types, cropping systems, and fertilization practices. Our results indicated that combined UINIs were the most efficient, increasing crop yields by 5% and mitigating gaseous emissions by 51% compared to UIs or NIs alone. UINIs achieved these benefits by enhancing crop ammonium (NH 4 + ) availability through regulating urea hydrolysis and prolonging NH 4 + retention by suppressing nitrification in the soil. The CBA revealed that the overall economic benefits of UINIs application outweighed the costs, resulting in a net monetary benefit of $23.36 ha −1 , equivalent to a 6.4% increase in revenue. Both meta‐regression and random forest analyses suggested that UINIs performance was strongly influenced by factors such as N application rate, organic matter content, and soil pH. Notably, more substantial responses were observed in fine‐textured soils and/or crops exposed to high N fertilization rates. Acidic soils (pH 3 volatilization due to specific inhibitory interactions. In conclusion, these findings highlight UINIs beneficial impacts on crop productivity and environmental conservation, achieving a “win‐win” scenario by addressing various N‐loss challenges while enhancing economic outcomes. Further exploration and optimization of the interaction between climate, soil, plant, and management systems and the use of appropriate inhibitors are crucial for maximizing their positive impact on global climate and reaping corresponding economic benefits.

Dynamics of phytoplankton assemblages determined by the HPLC–PIGMENTUM approach and the related environmental variables in the northern Chinese sea - Long Yang; Zhengguo Cui; Jian Zhang; Hongwei Wang; Hanbai Wang; Di Zhang; Xiaokun Ding; Daojun Zha; Li Gao; Tao Jiang (Marine Pollution Bulletin, 2024)

Boosting seawater denitrification in an electrochemical flow cell - Ding Li; Shuang-Cheng Jiang; Jia-Fang Xie; Jian Zhang; Ying-Lian Zheng; Quan-Bao Zhao; Han-Qing Yu (Water Research, 2024)

Solvent-free Acrylate/BCB drop-on-demand (DOD) inkjet dielectric ink for 3D printing - Haoran Liu; Chenghao Wang; Lishuai Zong; Lingmei Jiang; Guangsheng Zhang; Zichun Ding; Zexian Jia; Changhong Xiao; Chao Li; Jinyan Wang; Xigao Jian (Chemical Engineering Journal, 2024)

Lead iodide secondary growth and π-π stack regulation for sequential perovskite solar cells with 23.62% efficiency - Zhangfeng Huang; Zhuowei Du; Zhu Ma; Yujie Zheng; Qian Zhang; Wei You; Junbo Yang; Tangjie Yu; Shanyue Hou; Guoming Li; Hao Du; Yixian Li; et al. (Chemical Engineering Journal, 2024)

Rational regulation of post-electrodialysis electrochromic anion exchange membranes via TiO2@Ag synergistically strengthens visible-light photocatalytic anti-contamination activity - Yuyang Yao; Yueyue Lu; Jingwen Xu; Jiacheng Yu; Liang Guo; Heda Ding; Jian Li; Junbin Liao; Edison Huixiang Ang; Zhenlu Shen; Jiangnan Shen (Water Research, 2024)

Aflatoxin B1 as a complicit in intestinal damage caused by Eimeria ovinoidalis in lambs: Novel insights to reveal parasite-gut battle - Pan Chen; Wen-li Ding; Bo-wen Xu; Mujeeb Ur Rehman; Kai-li Liu; Yan-feng He; Sen-yang Li; Fu-chun Jian; Shu-cheng(淑成) Huang(黄) (Science of The Total Environment, 2024)

Topological surface states in quasi-two-dimensional magnetic kagome metal EuTi3Bi4 - Zhicheng Jiang; Tongrui Li; Jian Yuan; Zhengtai Liu; Zhipeng Cao; Soohyun Cho; Mingfang Shu; Yichen Yang; Zhikai Li; Jiayu Liu; Jianyang Ding; Zhonghao Liu; et al. (Science Bulletin, 2024)

Carbon–sulfur–calcium isotopic variability of lower Cambrian shale-hosted carbonate concretions: Insights into growth mechanisms and calcium cycling - Xiqiang Zhou; Xiyuan Chen; Tongxuan Du; Jian Sun; Dongjie Tang; Run Li; Kang-Jun Huang; Yi Ding; Daizhao Chen (Sedimentary Geology, 2024)

Formation of a transparent soy protein hydrogel: Controlled thermal aggregation of protein using glutaminase - Tang-Hao Li; Yao-Qin Yang; Ding-Yang Lv; Gao-Shang Wang; Jian Guo; Zhi-Li Wan; Xiao-Quan Yang (Food Hydrocolloids, 2024)

An improved CSM-based design method for H-section aluminium slender columns under eccentric compression - Pengcheng Li; Guohan Chen; Hao Ding; Yunchang Huang; Tianhao Zhang; Gang Xiong; Bin Jian (Engineering Structures, 2024)

LPAR6 Participates in Neuropathic Pain by Mediating Astrocyte Cells via ROCK2/NF-κB Signal Pathway - Xiaoyi Fan; Ruitong Chu; Xin Jiang; Peng Ma; Yan Chu; Tong Hua; Mei Yang; Ruifeng Ding; Jian Li; Zhenghua Xiang; Hongbin Yuan (Molecular Neurobiology, 2024)

Neural substrates for regulating self-grooming behavior in rodents - Guanqing Li; Chanyi Lu; Miaomiao Yin; Peng Wang; Pengbo Zhang; Jialiang Wu; Wenqiang Wang; Ding Wang; Mengyue Wang; Jiahan Liu; Xinghan Lin; Jian-Xu Zhang; et al. (Journal of Zhejiang University-SCIENCE B, 2024)

Long-term straw return promotes accumulation of stable soil dissolved organic matter by driving molecular-level activity and diversity - Zhen Cheng; Anjie Li; Ruigang Wang; Qian Hu; Jian Zhou; Ming Li; Tiecheng Wang; Ding He; Lingyan Zhu (Agriculture, Ecosystems & Environment, 2024)

The association between short-term ozone exposure and fasting blood glucose levels in non-diabetic adults was more obvious in rural residents: the evidence from a typical “urban–rural dual structure” province in southwestern China - Xue-Jiao Li; Ling Li; Li Zhao; Ding-Yan Hu; Na-Na Ma; Hua Xiao; Da-Wei Li; Jie Zhou; Yi-Ying Wang; Ji Zhang; Tao Liu; Yue-Xu Jiang; et al. (Air Quality, Atmosphere & Health, 2024)

Integrative plant area index retrieval and spatiotemporal analysis in Taihu Lake Basin via synergistic active-passive remote sensing techniques - Jian Li; Yongshuang Ding; Tao Xie; Shuying Bai; Xuehong Zhang; Chao Wang (International Journal of Remote Sensing, 2024)

Exploring the cationic surfactant adsorption efficiency at concentrations relative to the critical micelle concentration by SA/SiO2 microspheres - Zhiying Li; Lei Zhao; Qing Ao; Ge Zhang; Dongqing Kang; Yingli Li; Jian Liu; Gongtao Ding; Zhongren Ma; Yeit Haan Teow; Mohd Shaiful Sajab; Zhiqiang Li; et al. (Journal of Environmental Management, 2024)

Residue changes, degradation, processing factors and their relation between physicochemical properties of pesticides in peanuts during multiproduct processing - Kai Cui; Jian Wang; Shuai Guan; Jingyun Liang; Liping Fang; Ruiyan Ding; Teng Li; Zhan Dong; Guoping Ma; Xiaohu Wu; Yongquan Zheng (Food Chemistry, 2024)

Supercapacitor-isolated water electrolysis for renewable energy storage - Qian He; Hui Sun; Wen-Tao Bi; Xin-Yuan Wang; Bing Li; Fang Li; Zhen-Guo Guo; Jun Ding; Jian-Bo He (Chemical Engineering Journal, 2024)

The Synergistic Effect Study of Lipopolysaccharide (LPS) and A53T-α-Synuclein: Intranasal LPS Exposure on the A53T-α-Synuclein Transgenic Mouse Model of Parkinson’s Disease - Qing He; Shuzhen Zhang; Jian Wang; Tengfei Ma; Ding Ma; Li Wu; Mengxi Zhou; Lei Zhao; Yajing Chen; Jianren Liu; Wei Chen (Molecular Neurobiology, 2024)

The romantic history of signaling pathway discovery in cell death: an updated review - Lei-Yun Wang; Xing-Jian Liu; Qiu-Qi Li; Ying Zhu; Hui-Li Ren; Jia-Nan Song; Jun Zeng; Jie Mei; Hui-Xiang Tian; Ding-Chao Rong; Shao-Hui Zhang (Molecular and Cellular Biochemistry, 2024)

A Co-evolutionary Multi-population Evolutionary Algorithm for Dynamic Multiobjective Optimization - Xin-Xin Xu; Jian-Yu Li; Xiao-Fang Liu; Hui-Li Gong; Xiang-Qian Ding; Sang-Woon Jeon; Zhi-Hui Zhan (Swarm and Evolutionary Computation, 2024)

Safety and environmental protection application of high performance solid waste unburned ceramsite and its lightweight high strength concrete - Kai-jing Tang; Hong-na An; Chuan-bei Liu; Ying-ding Li; Lu-jun Jia; Yun Tang; Qi-qiang Wang; Yong Jiang; Zi-jian Song (Sustainable Chemistry and Pharmacy, 2024)

Effects of sulfite and freezing co-pretreatment on the volatile fatty acids production of waste activated sludge in anaerobic fermentation - Li-Li Yang; Yong Zhang; Hui Wang; Jian Huang; Yi-Fan Xiao; Jia-Qi Liu; Can Li; Ding-Cheng Hu; Chuan-Chuan Yan (Journal of Water Process Engineering, 2024)

Enhanced photocatalytic U(VI) reduction via double internal electric field in CoWO4/covalent organic frameworks p-n heterojunction - Rui-Xiang Bi; Zhi-Hai Peng; Lan Lei; Xiao-Xing Wang; Xin Liu; Li Zhang; Ru-Ping Liang; Jian-Ding Qiu (Journal of Hazardous Materials, 2024)

New simple method for calculating large-strain consolidation settlement of layered soft soils with horizontal drains and vacuum preloading with comparison to test data - Ze-jian Chen; Peng-lin Li; An Li; Jian-hua Yin; Ding-bao Song (Geotextiles and Geomembranes, 2024)

A state-of-the-art review on the dynamic design of nonlinear energy sinks - Xiao-Feng Geng; Hu Ding; Jin-Chen Ji; Ke-Xiang Wei; Xing-Jian Jing; Li-Qun Chen (Engineering Structures, 2024)

sp2-c linked Cu-based metal-covalent organic framework for chemical and photocatalysis synergistic reduction of uranium - Jin-Lan Liu; Mu-Xiang Lin; Juan Huang; Cheng-Rong Zhang; Jia-Xin Qi; Yuan-Jun Cai; Xiao-Juan Chen; Li Zhang; Ru-Ping Liang; Jian-Ding Qiu (Chemical Engineering Journal, 2024)

Recombination of variable and host range regions of glycoprotein gp85 in different avian leukosis virus subgroup K isolates - Xiyue Li; Yajun Wang; Jiufeng Li; Zuhua Yu; Ying Wei; Songbiao Chen; Lei He; Ke Ding; Jian Chen (Archives of Virology, 2024)

The loss of dissolved organic matter from biological soil crust at various successional stages under rainfall of different intensities: Insights into the changes of molecular components at different rainfall stages - Hao Wang; Qing-wei Zhang; Guo Chen; Xuan Li; Qi-lin Wang; Li Gao; Jian Wang; Ding He; Ming Li (Water Research, 2024)

Bacterial structures and their associated ARGs in Shanghai subway air, China - Lijun Zhang; Xiaojing Li; Yongping Liu; Yi Zheng; Lisha Shi; Yichen Ding; Jian Chen; Ping Xiao (Journal of Aerosol Science, 2024)

Axisymmetric finite strain consolidation model for soft soil consolidation with vertical drains under combined loading considering creep and non-Darcy flow - Peng-Lin Li; Zhen-Yu Yin; Ding-Bao Song; Jian-Hua Yin; Yu Pan (Geotextiles and Geomembranes, 2024)

New insights into anti-hyperuricemic effects of novel peptides from Antarctic Krill (Euphausia superba) by Q-Exactive Orbitrap MS-based non-targeted metabolomics - Li Hao; Yulian Ding; Yan Fan; Chensi Xia; Yuqian Meng; Qiannan Jia; Jian Zhang; Changhu Xue; Hu Hou (Food Bioscience, 2024)

Boosting persulfate activation through efficient π → π* transition activated by Cu ion anchored porphyrin-based metal–organic framework - Wen-Qiang Li; Oleksandr Savateev; Yuan-Ming Li; Jian-Kang Zheng; Yi-Xuan Wang; Nannan Hou; Xiao-Cheng Liu; Rong-Rong Ding; Xiao-Guo Zhou; Yang Wang; Xian-Yang Shi; Yang Mu (Chemical Engineering Journal, 2024)

Expert Consensus on Big Data Collection of Skin and Appendage Disease Phenotypes in Chinese - Shuang Zhao; Zhongling Luo; Ying Wang; Xinghua Gao; Juan Tao; Yong Cui; Aijun Chen; Daxing Cai; Yan Ding; Heng Gu; Jianying Gu; Chao Ji; et al. (Phenomics, 2024)

Green synthesis of nZVI-modified biochar significantly enhanced the removal of Cr(VI) from aqueous solution - Fengfeng Ma; Hao Zhao; Xudong Zheng; Jian Zhang; Weixuan Ding; Yaxian Jiao; Qing Li; Hongbing Kang (Environmental Science and Pollution Research, 2024)

Residue levels, processing factors and risk assessment of pesticides in ginger from market to table - Kai Cui; Jian Wang; Guoping Ma; Shuai Guan; Jingyun Liang; Liping Fang; Ruiyan Ding; Teng Li; Zhan Dong; Xiaohu Wu; Yongquan Zheng (Journal of Hazardous Materials, 2024)

Over 30% external quantum efficiency for doping-free D-A-type thermally activated delayed fluorescence organic light-emitting diodes - Yang Li; Yixia Liu; Yang Gao; Kai Zhang; Yan-Qiu Sun; Lei Ding; Man-Keung Fung; Jian Fan (Chemical Engineering Journal, 2024)

Phosphorylated covalent organic framework/graphene composites for photoelectrothermal integrated collaborative reduction of uranium - Rui Zhang; Liang Tao; Cheng-Peng Niu; Cheng-Rong Zhang; Tie-Ying Shi; Xiao-Xing Wang; Ying-Ao Wang; Li Zhang; Ru-Ping Liang; Jian-Ding Qiu (Chemical Engineering Journal, 2024)

Excellent energy storage performance of lead-based antiferroelectric ceramics via enhancing dielectric breakdown mechanism - Jian Zhou; Zisheng Xu; Huilin Yang; Limin Chu; Liming Chen; Hangren Li; Jianxiang Ding; Songlin Ran; Zhengming Sun; Xihong Hao (Chemical Engineering Journal, 2024)

Advanced “turn-on” colorimetric uranium platform based on the enhanced nanozyme activity of a donor-acceptor structured covalent organic framework - Sai Jin Xiao; Jing Huang; An Ting Qiu; Guang Zhou Liu; Li Zhang; Ting Wu; Ya Di Shi; Jian-Ding Qiu (Analytica Chimica Acta, 2024)

Non-fitting functional representation for the equilibrium constant subject to reaction between H2S and CO2 - Chao-Wen Wang; Ji Li; Lie-Hui Zhang; Qun-Chao Ding; Guan-Hong Liu; Gao Li; Rui Jiang; Xiao-Long Peng; Lin-Sheng Wei; Hong-Ming Tang; Jian-Yi Liu; Chun-Sheng Jia (Fuel, 2024)

Core-shell MOF@COF photocatalysts for synergistic enhanced U(VI) and tetracycline cleanup through space and carrier separation - Rui-Xiang Bi; Xin Liu; Lan Lei; Zhi-Hai Peng; Xiao-Xing Wang; Li Zhang; Ru-Ping Liang; Jian-Ding Qiu (Chemical Engineering Journal, 2024)

Bifunctional interface of metal–organic framework synergized with bismuth endows high stable zinc anode - Jian He; Wanhai Zhou; Jinchi Li; Shiqi Chen; Ding Zhu; Yungui Chen (Chemical Engineering Journal, 2024)

Organic nutrient availability and extracellular enzyme activities influence harmful algal bloom proliferation in a coastal aquaculture area - Lin-Jian Ou; Zhou Wang; Guang-Mao Ding; Feng-Xian Han; Jin-Yi Cen; Xin-Feng Dai; Ke-Qiang Li; Song-Hui Lu (Aquaculture, 2024)

The inventory of pollutants in brownfield sites: An innovative strategy for prevention and control of soil pollution in China - Ye Li; Tianhao He; Fangfang Ding; Xiaofei Li; Ye Huang; Erkai He; Hongming Cai; Peili Shi; Jian Liu; Yan Li; Ruijuan Qu; Wang Zheng; et al. (Science Bulletin, 2024)

Efficient capture of iodine in steam and water media by hydrogen bond-driven charge transfer complexes - Li Zhang; Yu-Ting Luo; Jia-Qi Fan; Sai-Jin Xiao; Qiong-Qing Zheng; Xiao-Lin Liu; Quan-Gen Tan; Chen Sun; Qiang Shi; Ru-Ping Liang; Jian-Ding Qiu (Journal of Hazardous Materials, 2024)

Regulatory effect of trehalose metabolism on chitin synthesis in Spodoptera frugiperda (J. E. Smith) (Lepidoptera: Noctuidae) as determined using RNAi - Yan-qi Yang; Yu-jian Liang; Jun-rui Zhi; Ding-yin Li; Cao Li (Journal of Asia-Pacific Entomology, 2024)

Biological activities and mass fragmentation pathways of meroterpenoid cochlioquinones from plant pathogenic fungus Bipolaris sorokiniana - Qi Li; Jian-zi Liu; Jian Yang; Yan-duo Wang; Sheng-Xiang Yang; Shu-bin Niu; Gang Ding (Food Chemistry, 2024)

Enhanced Beta2-band Oscillations Denote Auditory Hallucination in Schizophrenia Patients and a Monkey Model of Psychosis - Shuo Ma; Tianzhen Chen; Wenjun Jia; Jie Liu; Shihan Ding; Puzhe Li; Hong Gan; Dapeng Zhang; Shuxin Shao; Mu-Ming Poo; Min Zhao; Bomin Sun; et al. (Neuroscience Bulletin, 2024)

Seasonal variation, source apportionment, and cancer risk assessment of PM2.5-bound phthalates: a case study in Taiyuan, China - Wen-Jun Hong; Xun Wang; Jin-Jian Ding; Jian-Ming Jiang; Min-Jie Li; Shaoyang Ji; Nan Sang; Liang-Hong Guo (Air Quality, Atmosphere & Health, 2024)

Metabolomics analysis to interpret changes in physiological and metabolic responses to chronic heat stress in Pekin ducks - Xiangyi-Yi Zeng; Arshad Javid; Gang Tian; Ke-Ying Zhang; Shi-Ping Bai; Xue-Mei Ding; Jian-Ping Wang; Li Lv; Yue Xuan; Shan-Shan Li; Qiu-Feng Zeng (Science of The Total Environment, 2024)

Greenhouse cultivation enhances pesticide bioaccumulation in cowpeas following repeated spraying - Kai Cui; Jian Wang; Guoping Ma; Shuai Guan; Jingyun Liang; Liping Fang; Teng Li; Zhan Dong; Ruiyan Ding; Xiaohu Wu; Yongquan Zheng (Journal of Environmental Management, 2024)

Rapid in situ regeneration of phenol-saturated activated carbon fiber by an electro-permonosulfate-ozone process: Performance, operators and mechanism - Qin Xue; Biyu Yu; Mehary Dagnew; Wenli Li; Haojie Ding; Jian Zhang; Zhihua Sun; Pu Wang; Chun Zhao (Journal of Environmental Chemical Engineering, 2024)

Effect of egg white protein on the protein structure of highland barley noodles during processing - Xiangli Ding; Zhen-Yang Quan; Wen-Ping Chang; Lun Li; Jian-Ya Qian (Food Chemistry, 2024)

Efficient breeding and growth advantage of all-male population in Lanzhou catfish (Silurus lanzhouensis) - Jun-Sheng Niu; Tao Wang; Zhi Li; Zhong-Wei Wang; Miao Ding; Ming-Tao Wang; Zong-Qiang Lian; Jie Mei; Yang Wang; Li Zhou; Xiao-Juan Zhang; Jian-Fang Gui; et al. (Aquaculture, 2024)

Interfacial coordination-assisted construction of mechanically robust, fluorescent and intumescent flame retardant epoxy resins - Xin-Miao Li; Wei-Bin Bai; Yu-Cai Lin; Fu-Chuan Ding; Rong-Kun Jian (Chemical Engineering Journal, 2024)

FGF-18 Protects the Injured Spinal cord in mice by Suppressing Pyroptosis and Promoting Autophagy via the AKT-mTOR-TRPML1 axis - Feida Li; Tingwen Cai; Letian Yu; Gaoxiang Yu; Haojie Zhang; Yibo Geng; Jiaxuan Kuang; Yongli Wang; Yuepiao Cai; Jian Xiao; Xiangyang Wang; Jian Ding; et al. (Molecular Neurobiology, 2024)

Environmental stressors altered the groundwater microbiome and nitrogen cycling: A focus on influencing mechanisms and pathways - Jian Li; Lei Yang; Shihang Yu; Aizhong Ding; Rui Zuo; Jie Yang; Xiaofei Li; Jinsheng Wang (Science of The Total Environment, 2023)

Enhanced generation of oxysulfur radicals by the BiOBr/Montmorillonite activated sulfite system: Performance and mechanism - Hussein Abdelraouf; Fanyang Zhou; Yulong Li; Jiayi Ren; Guanshu Zhao; Qingliang Zhao; Jian Wei; Xuedong Zhai; Jing Ding (Environmental Research, 2023)

Ultra-fast degradation of ciprofloxacin by the peroxymonosulfate activation using a Co/Al-LDH decorated magnetic hydrochar: Structural design, catalytic performance and synergistic effects - Jian Zhang; Jia-Fang Xie; Jia-Cheng E. Yang; Ding Li; Lu-Bin Zhong; Yu-Ming Zheng (Chemical Engineering Journal, 2023)

In situ synthesis of bi-functional NH2-Ti2C3Tx@COF Schottky heterojunction through interfacial electron effects for enhancing U(VI) photoreduction - You-Gan Wang; Wei Jiang; Xin Liu; Li Zhang; Ru-Ping Liang; Jian-Ding Qiu (Chemical Engineering Journal, 2023)

Urban surface classification using semi-supervised domain adaptive deep learning models and its application in urban environment studies - Xiaotian Ding; Yifan Fan; Yuguo Li; Jian Ge (Environmental Science and Pollution Research, 2023)

The fate of microplastic pollution in the Changjiang River estuary: A review - Yifei Li; Qingbing Lu; Jian Yang; Yi Xing; Wei Ling; Kai Liu; Qizhen Yang; Hongjie Ma; Zengxin Pei; Tianqi Wu; Haochen Guo; Ziyuan Gao; et al. (Journal of Cleaner Production, 2023)

A facile strategy for fabricating structural rice-pea binary protein-based gel: Characterization and formation mechanism - Jian Ding; Tong Xu; Zhihai Li; Xinyang Sun; Xiaoyi Jiang; Fengjiao Fan; Qu Yan; Fan Yang; Peng Li; Yong Fang (Journal of Cereal Science, 2023)

Determination of vitamin K in infant formulas by liquid chromatography–online electrochemical reduction based on porous Pt/Ti electrode-fluorescence detection - Zhenzhen Wang; Chaoyang Sun; Shuchao Wu; Siyuan Ding; Lingxia Chen; Liying Wu; Jian Lou; Bin Xia; Li Wang (Food Chemistry, 2023)

Sulforaphane alleviates the meiosis defects induced by 3-nitropropionic acid in mouse oocytes - Wei-Jian Li; Xuan Zhang; Ming Shen; Hong-Lin Liu; Li-Ren Ding (Food and Chemical Toxicology, 2023)

Analysis of the spatial-temporal evolution of Green and low carbon utilization efficiency of agricultural land in China and its influencing factors under the goal of carbon neutralization - Jun Fu; Rui Ding; Yu-qi Zhu; Lin-yu Du; Si-wei Shen; Li-na Peng; Jian Zou; Yu-xuan Hong; Juan Liang; Ke-xin Wang; Wen-qian Xiao (Environmental Research, 2023)

Kilogram-scale synthesis of carbon dots with high-efficiency full-color solid-state fluorescence using an aggregation-induced emission strategy - Hui Ding; Ran Zhao; Zi-Hui Zhang; Jia-Jia Yang; Zheng Wang; Lu-Lan Xiao; Xue-Hua Li; Xin-Jian He; Huan-Ming Xiong (Chemical Engineering Journal, 2023)

Utilizing internal resonant scattering to improve photoluminescence energy outcoupling of CsPbBr3/Cs4PbBr6 perovskite phosphor - Zong-Tao Li; Bo-Jia Li; Jia-Sheng Li; Cun-Jiang Song; Xin-Rui Ding; Hai-Long Yuan; Bin-Hai Yu; Yong Tang; Jian-Zhen Ou; Romain Gautier; Hong-Lei Ji; Hao-Chung Kuo (Chemical Engineering Journal, 2023)

A stable spherical MOF-derived Mnx-Fe2O3/C catalysts for low-temperature CO-SCR - Cheng Li; Yong Shi; Qi Dong Zhao; Wei Xiong; Yue Ding; Jian Heng Sun; Ying Lei Huang; Zhong Fei Zhao (Chemical Engineering Journal, 2023)

The Relationship Between Cortical Morphological and Functional Topological Properties and Clinical Manifestations in Patients with Posttraumatic Diffuse Axonal Injury: An Individual Brain Network Study - Fuqing Zhou; Lin Wu; Long Qian; Hongmei Kuang; Jie Zhan; Jian Li; Gerald L. Cheung; Aimin Ding; Honghan Gong (Brain Topography, 2023)

Surface microrelief induced by tillage management alters the pathway and composition of dissolved organic matter exports from soils to runoff during rainfall - Hao Wang; Qingwei Zhang; Xuan Li; Yuanbi Yi; Qilin Wang; Li Gao; Jian Wang; Ding He; Ming Li (Water Research, 2023)

Dissipation, metabolism, accumulation, processing and risk assessment of fluxapyroxad in cucumber and cowpea vegetables from field to table - Kai Cui; Shuai Guan; Jingyun Liang; Liping Fang; Ruiyan Ding; Jian Wang; Teng Li; Zhan Dong; Xiaohu Wu; Yongquan Zheng (Food Chemistry, 2023)

Characterization of the physiochemical properties, microstructure, and molecular interactions of a novel rice-pea protein gel - Tong Xu; Xinyang Sun; Qu Yan; Zhihai Li; Wei Cai; Jian Ding; Fengjiao Fan; Peng Li; Pamela Drawbridge; Yong Fang (Food Chemistry, 2023)

Unraveling the synergistic effects and mechanisms of nano-carbon modification on metal hydride alloys for enhanced electrochemical performance in energy storage applications - Jinchi Li; Shuqi Yu; Ding Zhu; Wanhai Zhou; Jian He; Liang Zeng; Shiqi Chen; Bihua Ma; Haonan Xi; Chaoling Wu; Wanglai Cen; Yao Wang; et al. (Chemical Engineering Journal, 2023)

Thienoacene-fused fluorophores for highly efficient deep red/near-infrared OLEDs - Li Zhu; Yixia Liu; Xiaofei Wang; Kai Zhang; Jing-Wen Tai; Yan-Qiu Sun; Chuan-Kui Wang; Lei Ding; Man-Keung Fung; Jian Fan (Chemical Engineering Journal, 2023)

Construction of a CHO cell line with site-specific integration to stably express exogenous proteins using the CRISPR–Cas9 technique - Xuefeng Ding; Yun Chen; Hao Wu; Zhaoqi Yang; Yanfei Cai; Yunfeng Dai; Qinghe Xu; Jian Jin; Huazhong Li (Systems Microbiology and Biomanufacturing, 2023)

Construction of covalent organic framework nanozymes with photo-enhanced hydrolase activities for colorimetric sensing of organophosphorus nerve agents - Sai-Jin Xiao; Ming-Yue Yuan; Ya-Di Shi; Meng-Ping Wang; Hui-Han Li; Li Zhang; Jian-Ding Qiu (Analytica Chimica Acta, 2023)

Conversion of natural coastal wetlands to mariculture ponds dramatically decreased methane production by reducing substrate availability - Yanhong Dong; Junji Yuan; Junjie Li; Deyan Liu; Ye Qiu; Xin Zhang; Jian Xiang; Weixin Ding (Agriculture, Ecosystems & Environment, 2023)

Effects of Weight Gain During Pregnancy in Normal-Weight Women on Changes in the Gut Microbiota of Pregnant Women in the Third Trimester - Fengping Fu; Fengqin Wang; Jian Ding; Li Xiao; Xia Song (Biochemical Genetics, 2023)

Contaminant occurrence, water quality criteria and tiered ecological risk assessment in water: A case study of antifouling biocides in the Qiantang River and its estuary, Eastern China - Hai-Wei Luo; Jian-Ming Jiang; Xun Wang; Minjie Li; Jin-Jian Ding; Wen-Jun Hong; Liang-Hong Guo (Marine Pollution Bulletin, 2023)

Vegetation structural shift tells environmental changes on the Tibetan Plateau over 40 years - Yanfen Wang; Kai Xue; Ronghai Hu; Boyang Ding; Hong Zeng; Ruijin Li; Bin Xu; Zhe Pang; Xiaoning Song; Congjia Li; Jianqing Du; Xiuchun Yang; et al. (Science Bulletin, 2023)

Electrospun polyvinyl alcohol-chitosan dressing stimulates infected diabetic wound healing with combined reactive oxygen species scavenging and antibacterial abilities - Haibing Liu; Rong Chen; Pinkai Wang; Jinlang Fu; Zinan Tang; Jiajun Xie; Yanhong Ning; Jian Gao; Qiang Zhong; Xin Pan; Ding Wang; Mingyuan Lei; et al. (Carbohydrate Polymers, 2023)

Association of Blood Heavy Metal Exposure with Atherosclerotic Cardiovascular Disease (ASCVD) Among White Adults: Evidence from NHANES 1999–2018 - Kai Wang; Yukang Mao; Zheng Liu; Yansong Li; Zhongming Li; Yan Sun; Yinzhang Ding; Xianling Liu; Jian Hong; Di Xu; Jing Zhang (Biological Trace Element Research, 2023)

Hypothermic neuroprotection by targeted cold autologous blood transfusion in a non-human primate stroke model - Jian Chen; Shuaili Xu; Hangil Lee; Longfei Wu; Xiaoduo He; Wenbo Zhao; Mo Zhang; Yanhui Ma; Yuchuan Ding; Yongjuan Fu; Chuanjie Wu; Ming Li; et al. (Science Bulletin, 2023)

Ergostane-type sterols and sesquiterpenes with anti-neuroinflammatory activity from a Nigrograna species associated with Clematis shensiensis - Liang-Liang Zhai; Ting-Ting Jiang; Rong Zhang; Jian-Nan Li; Yi-Jie Zhai; Qiang Zhang; Ding Li; Wen-Bo Han (Phytochemistry, 2023)

How far are green products from the Chinese dinner table? ——Chinese farmers’ acceptance of green planting technology - Zehong Li; Yan Ding; Jian Chen; Minyan Zhao (Journal of Cleaner Production, 2023)

Preparation of germinated brown rice with high γ-aminobutyric acid content and short root by magnetic field treatment - Caiwen Chen; Yang Tao; Yongbin Han; Yanfeng Ding; Xingliang Jian; Dandan Li (Journal of Cereal Science, 2023)

The widespread presence of triazole fungicides in greenhouse soils in Shandong Province, China: A systematic study on human health and ecological risk assessments - Zhan Dong; Kai Cui; Jingyun Liang; Shuai Guan; Liping Fang; Ruiyan Ding; Jian Wang; Teng Li; Shengying Zhao; Zhongni Wang (Environmental Pollution, 2023)

Chitinolyticbacter albus sp. Nov., A Novel Chitin-Degrading Bacterium Isolated from Ancient Wood Rhizosphere Soil - Meng-Yu Zhang; Jiang-Yuan Zhao; Le-Le Li; Cheng Ling; Jing Tang; Song-Guo Liang; Jian-Yu Li; Xiao-Di Liu; Lu-Yao Feng; Pei-Wen Yang; Zhu-Feng Shi; Zhang-Gui Ding; et al. (Current Microbiology, 2023)

Enhanced potassium-ion storage performance of bimetallic-sulfide based on regulatory reaction mechanism - Shengyang Li; Hao Chen; Qiusheng Zhang; Hongli Deng; Song Chen; Xiaohua Shen; Yizhi Yuan; Yifang Ding; Yingliang Cheng; Hongtao Sun; Jian Zhu; Bingan Lu (Chemical Engineering Journal, 2023)

NLRP7 participates in the human subcortical maternal complex and its variants cause female infertility characterized by early embryo arrest - Jian Han; Nana Zhang; Qiqi Cao; Xiaodan Shi; Congjing Wang; Ximan Rui; Jie Ding; Chun Zhao; Junqiang Zhang; Xiufeng Ling; Hong Li; Yichun Guan; et al. (Journal of Molecular Medicine, 2023)

Pseudomonas subflava sp. nov., a new Gram-negative bacterium isolated from Guishan in Yunnan province, south–west China - Cheng Ling; Jiang-Yuan Zhao; Le-Le Li; Zhang-Gui Ding; Meng-Yu Zhang; Jing Tang; Song-Guo Liang; Jian-Yu Li; Xiao-Di Liu; Lu-Yao Feng; Pei-Wen Yang; Yao Lu; et al. (Antonie van Leeuwenhoek, 2023)

Spatiotemporal analysis of bike mobility chain: A new perspective on mobility pattern discovery in urban bike-sharing system - Rui Xin; Jian Yang; Bo Ai; Linfang Ding; Tingting Li; Ruoxin Zhu (Journal of Transport Geography, 2023)

Ag quantum dots decorated ultrathin g-C3N4 nanosheets for boosting degradation of pharmaceutical contaminants: Insight from interfacial electric field induced by local surface plasma resonance - Zhenzhou Wang; Danqi Wang; Fang Deng; Xinggang Liu; Xibao Li; Xubiao Luo; Yanzhi Peng; Jian Zhang; Jianping Zou; Lin Ding; Longshuai Zhang (Chemical Engineering Journal, 2023)

Biomarkers of aging - Hainan Bao; Jiani Cao; Mengting Chen; Min Chen; Wei Chen; Xiao Chen; Yanhao Chen; Yu Chen; Yutian Chen; Zhiyang Chen; Jagadish K. Chhetri; Yingjie Ding; et al. (Science China Life Sciences, 2023)

Klotho improves cardiac fibrosis, inflammatory cytokines, ferroptosis, and oxidative stress in mice with myocardial infarction - Kai WANG; Zhongming LI; Yinzhang DING; Zheng LIU; Yansong LI; Xianling LIU; Yan SUN; Jian HONG; Wei ZHENG; Lijun QIAN; Di XU (Journal of Physiology and Biochemistry, 2023)

Discovery of a natural small-molecule AMP-activated kinase activator that alleviates nonalcoholic steatohepatitis - Jin Chen; Li Xu; Xue-Qing Zhang; Xue Liu; Zi-Xuan Zhang; Qiu-Mei Zhu; Jian-Yu Liu; Muhammad Omer Iqbal; Ning Ding; Chang-Lun Shao; Mei-Yan Wei; Yu-Chao Gu (Marine Life Science & Technology, 2023)
Non-alcoholic steatohepatitis (NASH) is a primary cause of cirrhosis and hepatocellular carcinoma. Unfortunately, there is no approved drug treatment for NASH. AMP-activated kinase (AMPK) is an important metabolic sensor and whole-body regulator. It has been proposed that AMPK activators could be used for treating metabolic diseases such as obesity, type 2 diabetes and NASH. In this study, we screened a marine natural compound library by monitoring AMPK activity and found a potent AMPK activator, candidusin A ( CHNQD-0803 ). Further studies showed that CHNQD-0803 directly binds recombinant AMPK with a K D value of 4.728 × 10 –8 M and activates AMPK at both molecular and intracellular levels. We then investigated the roles and mechanisms of CHNQD-0803 in PA-induced fat deposition, LPS-stimulated inflammation, TGF-β-induced fibrosis cell models and the MCD-induced mouse model of NASH. The results showed that CHNQD-0803 inhibited the expression of adipogenesis genes and reduced fat deposition, negatively regulated the NF-κB-TNFα inflammatory axis to suppress inflammation, and ameliorated liver injury and fibrosis. These data indicate that CHNQD-0803 as an AMPK activator is a novel potential therapeutic candidate for NASH treatment.

Determination of protein-bound α-amanitin in mouse plasma: A potential new indicator of poisoning with the mushroom toxin α-amanitin - Zhijun Wu; Jing Dai; Jingguang Fan; Chunguang Ding; Wenjin Zhao; Chengmin Yu; Qunmei Yao; Jian Sun; Haijiao Li; Chengye Sun (Toxicon, 2023)

Experiment study on seismic behavior of squat UHPC shear walls subjected to tension-shear combined cyclic load - Yue-Yi Li; Ran Ding; Jian-Guo Nie (Engineering Structures, 2023)

Machine learning-assisted mapping of city-scale air temperature: Using sparse meteorological data for urban climate modeling and adaptation - Xiaotian Ding; Yongling Zhao; Yifan Fan; Yuguo Li; Jian Ge (Building and Environment, 2023)

Phytochemical and chemotaxonomic investigations on the aerial parts of Cynanchum auriculatum Royle ex Wight - Yanling Xu; Chenyang Wu; Lu Wang; Shengbo Wu; Yueru Chen; Xiaoxue Ding; Lin Wang; Yi Yu; Weiming Du; Yuqing Zhang; Rachel Y.H. Yang; Jian Hong; et al. (Biochemical Systematics and Ecology, 2023)

Antibiotic resistance and resistance mechanism of Corynebacterium kroppenstedtii isolated from patients with mastadenitis - Qin Zhang; Shi Wu; Peipei Song; Yi Liu; Li Ding; Qingyu Shi; Xuan Zhu; Liyuan Zhang; Jun Zhang; Qin Wang; Jian Xu; Fupin Hu (European Journal of Clinical Microbiology & Infectious Diseases, 2023)

An in-situ strategy to construct uracil-conjugated covalent organic frameworks with tunable fluorescence/recognition characteristics for sensitive and selective Mercury(II) detection - Xi-Rui Deng; A-Wei Hu; Sheng-Qian Hu; Wen-Li Yang; Chen Sun; Sai-Jin Xiao; Gui-Ping Yang; Qiong-Qing Zheng; Ru-Ping Liang; Li Zhang; Jian-Ding Qiu (Analytica Chimica Acta, 2023)

Obeticholic acid protects against methamphetamine-induced anxiety-like behavior by ameliorating microbiota-mediated intestinal barrier impairment - Jian-Zheng Yang; Kai-Kai Zhang; Jie-Tao He; Li-Jian Chen; Jin-Feng Ding; Jia-Li Liu; Jia-Hao Li; Yi Liu; Xiu-Wen Li; Dong Zhao; Xiao-Li Xie; Qi Wang (Toxicology, 2023)

Distinguishing the contributions of hot holes from interband and intraband transitions to the photoenhanced electrocatalytic oxidation reaction of ethanol - Chen Chi; Miao Ni; Xin-Lei Ding; Dong-Rui Yang; Jian Li; Xing-Hua Xia (Science Bulletin, 2023)

Heavy-metal resistant bio-hybrid with biogenic ferrous sulfide nanoparticles: pH-regulated self-assembly and wastewater treatment application - Xian-Zhong Fu; Jie Wu; Jie Li; Jian Ding; Shuo Cui; Xue-Meng Wang; Yun-Jie Wang; Hou-Qi Liu; Xin Deng; Dong-Feng Liu; Wen-Wei Li (Journal of Hazardous Materials, 2023)

Olefin-linked cationic covalent organic frameworks for efficient extraction of ReO4−/99TcO4− - Wei-Rong Cui; Wei Xu; Yi-Ru Chen; Kai Liu; Wei-Bin Qiu; Yibao Li; Jian-Ding Qiu (Journal of Hazardous Materials, 2023)

Insight into the dynamic variation and retention of major aroma volatile compounds during the milling of Suxiang japonica rice - Zhihai Li; Xinyang Sun; Tong Xu; Wei Dai; Qu Yan; Peng Li; Yong Fang; Jian Ding (Food Chemistry, 2023)

Erratum to: Rigid block characteristics on subaerial landslide-tsunamis using a 3D coupled Eulerian-Lagrangian model - Yi-ding Bao; Jian-ping Chen; Li-jun Su; Xin Zhou; Cheng-shan Yin (Journal of Mountain Science, 2023)

Water quality criteria derivation and tiered ecological risk evaluation of antifouling biocides in marine environment - Hai-Wei Luo; Min Lin; Xin-Xin Bai; Bin Xu; Minjie Li; Jin-Jian Ding; Wen-Jun Hong; Liang-Hong Guo (Marine Pollution Bulletin, 2023)

Synthesis of cationic polymer decorated with halogen for highly efficient trapping 99TcO4-/ReO4- - You-Gan Wang; Qing-Hua Hu; Juan Huang; Wei Jiang; Li Zhang; Ru-Ping Liang; Jian-Ding Qiu (Journal of Hazardous Materials, 2023)

Seismic performance of squat UHPC shear walls subjected to high-compression shear combined cyclic load - Yue-Yi Li; Jian-Guo Nie; Ran Ding; Jian-Sheng Fan (Engineering Structures, 2023)

A green and designable natural deep eutectic solvent-based supramolecular solvents system: Efficient extraction and enrichment for phytochemicals - Zi-Hui Cai; Jian-Dong Wang; Lin Liu; Liu-Ding Ruan; Qi Gu; Xin-Yu Yan; Li-Na Fu; Peng-Quan Zhao; Su Zhang; Yu-Jie Fu (Chemical Engineering Journal, 2023)

Microplastics-derived dissolved organic matters accelerate photodegradation of sulfamethazine in wastewater ultraviolet disinfection process - Zeyuan Yang; Peng Liu; Jian Wang; Ling Ding; Luqi Li; Hanzhong Jia; Tiecheng Wang; Xuetao Guo; Shixiang Gao (Chemical Engineering Journal, 2023)

A 2D mesoporous hydrazone covalent organic framework for selective detection and ultrafast recovery of Au(III) from electronic waste - Li Zhang; Jia-Qi Fan; Qiong-Qing Zheng; Sai-Jin Xiao; Cheng-Rong Zhang; Shun-Mo Yi; Xin Liu; Wei Jiang; Quan-Gen Tan; Ru-Ping Liang; Jian-Ding Qiu (Chemical Engineering Journal, 2023)

Chemical constituents from the flowers of Cynanchum auriculatum Royle ex Wight - Xiaoxue Ding; Lu Wang; Yanling Xu; Shengnan Zheng; Shuang Wang; Lin Wang; Miao Qin; Shengbo Wu; Yi Yu; Jian Hong; Honglei Zhou; Lingchuan Xu; et al. (Biochemical Systematics and Ecology, 2023)

Elevated Levels of Naturally-Occurring Autoantibodies Against the Extracellular Domain of p75NTR Aggravate the Pathology of Alzheimer’s Disease - Chen-Yang He; Ding-Yuan Tian; Si-Han Chen; Wang-Sheng Jin; Yuan Cheng; Jia-Yan Xin; Wei-Wei Li; Gui-Hua Zeng; Cheng-Rong Tan; Jie-Ming Jian; Dong-Yu Fan; Jun-Rong Ren; et al. (Neuroscience Bulletin, 2023)

Rigid block characteristics on subaerial landslide-tsunamis using a 3D coupled Eulerian-Lagrangian model - Yi-ding Bao; Jian-ping Chen; Li-jun Su; Xin Zhou; Cheng-shan Yin (Journal of Mountain Science, 2023)

Review of research on migration, distribution, biological effects, and analytical methods of microfibers in the environment - Yifei Li; Qingbin Lu; Yi Xing; Kai Liu; Wei Ling; Jian Yang; Qizhen Yang; Tianqi Wu; Jiafu Zhang; Zengxin Pei; Ziyuan Gao; Xiaoyan Li; et al. (Science of The Total Environment, 2023)

Sources, characteristics, and in situ degradation of dissolved organic matters: A case study of a drinking water reservoir located in a cold-temperate forest - Fan Liu; Qingliang Zhao; Jing Ding; Lili Li; Kun Wang; Huimin Zhou; Miao Jiang; Jian Wei (Environmental Research, 2023)

Multifunctional, breathable MXene-PU mesh electronic skin for wearable intelligent 12-lead ECG monitoring system - Tianrui Cui; Yancong Qiao; Ding Li; Xiaorui Huang; Le Yang; Anzhi Yan; Zhikang Chen; Jiandong Xu; Xichao Tan; Jinming Jian; Zhen Li; Shourui Ji; et al. (Chemical Engineering Journal, 2023)

Pollution characteristics and non-dietary human cumulative risk assessment of neonicotinoids in vegetable greenhouse soils: a case study in Shandong Province, China - Kai Cui; Mingxiao Ning; Jingyun Liang; Shuai Guan; Liping Fang; Ruiyan Ding; Jian Wang; Teng Li; Zhan Dong (Journal of Soils and Sediments, 2023)

Brevibacillus daliensis sp. nov., Isolated From Soil in Machangqing Nature Reserve - Shi-Qiang Ye; Jiang-Yuan Zhao; Le-Le Li; Cheng Ling; Meng-Yu Zhang; Jing Tang; Song-Guo Liang; Jian-Yu Li; Pei-Wen Yang; Jiao Xiong; Lu-Yao Feng; Zhu-Feng Shi; et al. (Current Microbiology, 2023)

Research on time series InSAR monitoring method for multiple types of surface deformation in mining area - Ya-xing Li; Ke-ming Yang; Jian-hong Zhang; Zhi-xian Hou; Shuang Wang; Xin-ming Ding (Natural Hazards, 2022)

An alkali-resistant metal–organic framework as halogen bond donor for efficient and selective removing of ReO4−/TcO4− - Qing-Hua Hu; Yu-Zhen Shi; Xin Gao; Li Zhang; Ru-Ping Liang; Jian-Ding Qiu (Environmental Science and Pollution Research, 2022)

The distinct disrupted plasticity in structural and functional network in mild stroke with basal ganglia region infarcts - Hua Zhu; Lijun Zuo; Wanlin Zhu; Jing Jing; Zhe Zhang; Lingling Ding; Fengjuan Wang; Jian Cheng; Zhenzhou Wu; Yongjun Wang; Tao Liu; Zixiao Li (Brain Imaging and Behavior, 2022)

Negative air ion exposure ameliorates depression-like behaviors induced by chronic mild stress in mice - Yun-Qing Hu; Ting-Ting Niu; Jian-ming Xu; Li Peng; Qing-Hua Sun; Ying Huang; Ji Zhou; Yu-Qiang Ding (Environmental Science and Pollution Research, 2022)
The presence of negative air ions (NAI) is suggested to be a beneficial factor in improving psychological status and used in treating depression as an alternative approach. However, more biological evidence from animal models is needed to ensure the effects of NAI on the mood regulation, through which can facilitate identification of possible underlying mechanisms. In this study, the chronic mild stress (CMS) protocol was used to induce depressive-like behaviors in mice, and the effects of NAI exposure on CMS-induced depression-like behaviors were examined. Thirty-day NAI exposure prevented the CMS-induced depression-like behaviors as shown by the restoration of sucrose preference and reduced immobility time in the tail suspension test. In addition, the elevation of serous corticosterone was present in CMS-treated mice but not existed in those with the NAI exposure. Furthermore, we observed altered ratios of some cytokines secreted by type 1 T helper (Th1) cells and Th2 cells in CMS-treated mice, but it could be restored after NAI exposure. In conclusion, NAI intervention is able to ameliorate CMS-induced depression-like behaviors in mice, and this effect is associated with the alteration of corticosterone and functional rebalance between Th1 and Th2 cells.

Cohnella mopanensis sp. nov., a new Gram-negative bacterium isolated from soil in Xinping Mountain National Forest Park - Jing Tang; Jiang-Yuan Zhao; Le-Le Li; Zhang-Gui Ding; Shi-Qiang Ye; Cheng Ling; Meng-Yu Zhang; Song-Guo Liang; Jian-Yu Li; Pei-Wen Yang; Jiao Xiong; Lu-Yao Feng; et al. (Archives of Microbiology, 2022)

Revealing Selection in Breeding and Genetic Characteristics of Economically Important Traits of New Species of Apostichopus Japonicas Based on Genome Resequencing and GWAS Analysis - Chao Guo; Yuanxin Li; Jiahui Xie; Lingshu Han; Youquan Wang; Xianglei Zhang; YangLei Wu; Jian Song; Yaqing Chang; Jun Ding (Frontiers in Marine Science, 2022)
Apostichopus japonicas is an economically important species with high nutritional value. However, our knowledge of its genetic diversity and the genetic changes that occurred during its domestication or trait selection is quite limited. In this study, the whole genomes of 254 A . japonicas samples were resequenced. Analyses of the population genetic structure revealed that the genetic diversity of A. japonicas in the north of China is generally high, there was no difference in the population structure among the six cultured populations, and they were divided into two subpopulations together with AY-1 (new species). The results also showed that the genetic diversity of the AY-1 population was relatively low, the degree of linkage of alleles was high, and this population had been subjected to more positive selection. Based on Tajima’s D, F ST analysis, and ROD analysis, the selected intervals and genes of the AY-1 population were identified, with some of the candidate intervals being related to an economically important trait and breeding target, namely, the number of parapodia. Gene Ontology analysis of the candidate genes revealed that the two subpopulations differed in their immune function, protein synthesis, decomposition, and transport, among others. Using GWAS, we identified 39 candidate genes for four economically important traits of A. japonicas , and we verified that those genes contained non-synonymous SNPs. Through this verification, BSL78_00022 and BSL78_00023 were found to be key genes for the number of parapodia in A. japonicas . Of these two genes, BSL78_00022 encodes a protein related to cell differentiation and proliferation, so it was assumed that three non-synonymous substitutions (Ser-Phe, Glu-Asp, and Ala-Val) in this gene are related to the changes in the number of parapodia. Meanwhile, the pleiotropic gene BSL78_04631, which is related to body weight and body wall weight, and promotes protein synthesis and cell growth, has a non-synonymous substitution (IlE-Val), which is assumed to be the reason for the difference in body weight and body wall weight of A. japonicas . These results provide a new perspective for explaining the genetic structure characteristics of A. japonicas and analyzing the selection and economically important traits in the breeding of new species.

In situ stress state and seismic hazard in the Dayi seismic gap of the Longmenshan thrust belt - Bing Li; Furen Xie; Jinshui Huang; Xiwei Xu; Qiliang Guo; Guangwei Zhang; Junshan Xu; Jianxin Wang; Dawei Jiang; Jian Wang; Lifeng Ding (Science China Earth Sciences, 2022)

Formation and reactivation mechanisms of large-scale ancient landslides in the Longwu River basin in the northeast Tibetan Plateau, China - Jing-jing Tian; Tian-tao Li; Xiang-jun Pei; Feng Ding; Hao Sun; Xian-gang Xie; Jian Guo (Journal of Mountain Science, 2022)

Effective connectivity decreases in specific brain networks with postparalysis facial synkinesis: a dynamic causal modeling study - Zhen-Zhen Ma; Ye-Chen Lu; Jia-Jia Wu; Xu-Yun Hua; Si-Si Li; Wei Ding; Jian-Guang Xu (Brain Imaging and Behavior, 2022)

Effect of high temperature on the physical properties and pore structure characteristics of organic-rich shale - Yukang Li; Jian Xiong; Guocai Wu; Xiangjun Liu; Lixi Liang; Yi Ding; Feng Wu (Arabian Journal of Geosciences, 2022)

Recycling of supra-crustal materials in the rhyolites from north Sonid Youqi: implications for the crustal evolution in the southeast Central Asian Orogenic Belt - Jian-Zhou Tang; Zhicheng Zhang; Bo Liu; Shaohua Zhang; Ke Li; Qi Wang; Cong Ding (International Journal of Earth Sciences, 2022)

Transcriptomic and Metabolomic Analyses Provide Insights into the Growth and Development Advantages of Triploid Apostichopus japonicus - Jiahui Xie; Yi Sun; Yue Cao; Lingshu Han; Yuanxin Li; Beichen Ding; Chuang Gao; Pengfei Hao; Xin Jin; Yaqing Chang; Jian Song; Donghong Yin; et al. (Marine Biotechnology, 2022)
Polyploid breeding is widely used in aquaculture as an important area of new research. We have previously grown Apostichopus japonicus triploids with a growth advantage. The body length, body weight, and aestivation time of triploid and diploid A. japonicus were measured in this study, and the transcriptome and metabolome were used to examine the growth advantage of triploids A. japonicus . The results showed that the proportion of triploid A. japonicus with a body length of 6–12 cm and 12–18 cm was significantly higher than that of diploid A. japonicus , and triploid A. japonicus had a shorter aestivation time (39 days) than diploid (63 days). We discovered 3296 differentially expressed genes (DEGs); 13 DEGs (for example, cyclin-dependent kinase 2 ) related to growth advantage, immune regulation, and energy storage were screened as potential candidates. According to Gene Ontology (GO) enrichment analysis, DEGs were significantly enriched in the cytoplasm (cellular component), ATP binding process (molecular function), oxidation–reduction process (biological process), and other pathways. According to the Kyoto Encyclopedia of Genes and Genomes (KEGG) enrichment data, DEGs were significantly enriched in ribosome production and other areas. We discovered 414 significant differential metabolites (SDMs), with 11 important SDMs (for example, nocodazole) linked to a growth advantage. SDMs are significantly enriched in metabolic pathways, as well as other pathways, according to the KEGG enrichment results. According to a combined transcriptome and metabolome analysis, 6 DEGs have regulatory relationships with 11 SDMs, which act on 11 metabolic pathways together. Our results further enrich the biological data of triploid A. japonicus and provide useful resources for genetic improvement of this species.

Infectivity and antigenicity of pseudoviruses with high-frequency mutations of SARS-CoV-2 identified in Portugal - Hai-xin Wang; Li Zhang; Zi-teng Liang; Jian-hui Nie; Jia-jing Wu; Qian-qian Li; Ru-xia Ding; Yue Zhang; Guo-qing Chen; You-chun Wang; Hui-guo Wang; Wei-jin Huang (Archives of Virology, 2022)
Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) has had a major impact on global human health. During the spread of SARS-CoV-2, weakened host immunity and the use of vaccines with low efficacy may result in the development of more-virulent strains or strains with resistance to existing vaccines and antibodies. The prevalence of SARS-CoV-2 mutant strains differs between regions, and this variation may have an impact on the effectiveness of vaccines. In this study, an epidemiological investigation of SARS-CoV-2 in Portugal was performed, and the VSV-ΔG-G* pseudovirus system was used to construct 12 spike protein epidemic mutants, D614G, A222V+D614G, B.1.1.7, S477N+D614G, P1162R+D614G+A222V, D839Y+D614G, L176F+D614G, B.1.1.7+L216F, B.1.1.7+M740V, B.1.258, B.1.258+L1063F, and B.1.258+N751Y. The mutant pseudoviruses were used to infect four susceptible cell lines (Huh7, hACE2-293T-293T, Vero, and LLC-MK2) and 14 cell lines overexpressing ACE2 from different species. Mutant strains did not show increased infectivity or cross-species transmission. Neutralization activity against these pseudoviruses was evaluated using mouse serum and 11 monoclonal antibodies. The neutralizing activity of immunized mouse serum was not significantly reduced with the mutant strains, but the mutant strains from Portugal could evade nine of the 11 monoclonal antibodies tested. Neutralization resistance was mainly caused by the mutations S477N, N439K, and N501Y in the spike-receptor binding domain. These findings emphasize the importance of SARS-CoV-2 mutation tracking in different regions for epidemic prevention and control.

Monthly Streamflow Forecasting Using Convolutional Neural Network - Xingsheng Shu; Wei Ding; Yong Peng; Ziru Wang; Jian Wu; Min Li (Water Resources Management, 2021)

Emerging role of air pollution in chronic kidney disease - Yue Chen; Fan Cao; Jian-Ping Xiao; Xin-Yu Fang; Xue-Rong Wang; Li-Hong Ding; De-Guang Wang; Hai-Feng Pan (Environmental Science and Pollution Research, 2021)

Cloning and functional characterization of two GsSnRK1 gene promoters from wild soybean - Jun Chen; Qiang Li; Pengmin Zhang; Haoran Lu; Ya Bian; Yi Jian; Yizhu Wang; Xiaodong Ding; Jialei Xiao (Plant Biotechnology Reports, 2021)

Apportioning above- and below-ground effects of moss biocrusts on soil detachment by overland flow in a subtropical climate - Guan-hua Zhang; Liang Yi; Wen-feng Ding; Xu Lei; Yi-ran Wang; Bao-yang Sun; Jian-ming Li (Journal of Mountain Science, 2021)

The ATP Level in the mPFC Mediates the Antidepressant Effect of Calorie Restriction - Qian Wang; Ying Kong; Song Lin; Ding-Yu Wu; Jian Hu; Lang Huang; Wen-Si Zang; Xiao-Wen Li; Jian-Ming Yang; Tian-Ming Gao (Neuroscience Bulletin, 2021)

The Significant Role of Radiosonde-measured Cloud-base Height in the Estimation of Cloud Radiative Forcing - Hui Xu; Jianping Guo; Jian Li; Lin Liu; Tianmeng Chen; Xiaoran Guo; Yanmin Lyu; Ding Wang; Yi Han; Qi Chen; Yong Zhang (Advances in Atmospheric Sciences, 2021)

Individual variation in metabolic rate, locomotion capacity and hypoxia tolerance and their relationships in juveniles of three freshwater fish species - Xu Pang; De-Yong Pu; Dan-Yang Xia; Xiao-Hong Liu; Shi-Hua Ding; Yun Li; Shi-Jian Fu (Journal of Comparative Physiology B, 2021)

Molecular Regulatory Mechanism and Toxicology of Neurodegenerative Processes in MPTP/Probenecid-Induced Progressive Parkinson’s Disease Mice Model Revealed by Transcriptome - Weiwei Yang; Wenwen Hao; Zhuo Meng; Shiyan Ding; Xiaodi Li; Tao Zhang; Weixiao Huang; Lian Xu; Yu Zhang; Jian Yang; Xiaosong Gu (Molecular Neurobiology, 2021)
Parkinson’s disease (PD) is a neurodegenerative disease caused by a variety of unclear complex pathogenic factors. The 1-methyl-4-phenyl-1, 2, 3, 6-tetrahydropyridine/probenecid (MPTP/p)-induced progressive PD mice is a well-recognized classic model for studying PD, but the molecular toxicology of this model is still unclear. Here, for the first time, we report gradual neurodegenerative processes in MPTP/p-induced progressive PD mice model using RNA-seq. Transcriptional responses are orchestrated to regulate the expression of many genes in substantia nigra, such as Ntf3 , Pitx3 , Th , and Drd2 , leading to the degeneration of dopaminergic neurons at last. We proposed that the established model could be divided into three phases based on their molecular toxicological features: “the stress response phase” which maintained the microenvironment homeostasis, “the pre-neurodegenerative phase” which demonstrated observed MPTP/p cytotoxicity and gradual degeneration of dopaminergic neurons, and “the neurodegenerative phase” which reflected distinct damage and dopaminergic neuron apoptotic process. Glia cells exhibited a certain protective effect on dopaminergic neurons in 3rd and 6th MPTP/p-induced cytotoxicity. But in 10th MPTP/p injection, glia cells play a promoting role in PD and tissue damages caused by oxidative stress. This study also indicated that the substantia nigra of PD mice showed unique patterns of changes at each stage. Moreover, neurotrophic signaling pathway, ECM-receptor interaction, oxidative phosphorylation, apoptosis and necroptosis were enriched at 3rd and 6th MPTP/p injection, which might be associated with the PD progress. This study provided an extensive data set of molecular toxicology for elucidating of PD progression and offered comprehensive theoretical knowledge for the development of new therapy.

A Wearable Augmented Reality Navigation System for Surgical Telementoring Based on Microsoft HoloLens - Peng Liu; Chenmeng Li; Changlin Xiao; Zeshu Zhang; Junqi Ma; Jian Gao; Pengfei Shao; Ian Valerio; Timothy M. Pawlik; Chengbiao Ding; Alper Yilmaz; Ronald Xu (Annals of Biomedical Engineering, 2021)

Models and measurements of seven years of evapotranspiration on a high elevation site on the Central Tibetan Plateau - Li-hui Wang; Xiao-bo He; Jakob F. Steiner; Dong-wei Zhang; Jin-kui Wu; Shao-yong Wang; Yong-jian Ding (Journal of Mountain Science, 2020)

Analysis of provincial total-factor air pollution efficiency in China by using context-dependent slacks-based measure considering undesirable outputs - Ke-Liang Wang; Li-Li Ding; Jian-Min Wang; Mian Yang (Natural Hazards, 2020)

Erythropoietin-Induced Autophagy Protects Against Spinal Cord Injury and Improves Neurological Function via the Extracellular-Regulated Protein Kinase Signaling Pathway - Lin Zhong; Hui Zhang; Zheng-Fei Ding; Jian Li; Jin-Wei Lv; Zheng-Jun Pan; De-Xiang Xu; Zong-Sheng Yin (Molecular Neurobiology, 2020)

Effects of moss-dominated biocrusts on soil detachment by overland flow in the Three Gorges Reservoir Area of China - Guan-hua Zhang; Wen-feng Ding; Jian Pu; Jian-ming Li; Feng Qian; Bao-yang Sun (Journal of Mountain Science, 2020)

Eddy-resolving Simulation of CAS-LICOM3 for Phase 2 of the Ocean Model Intercomparison Project - Yiwen Li; Hailong Liu; Mengrong Ding; Pengfei Lin; Zipeng Yu; Yongqiang Yu; Yao Meng; Yunlong Li; Xiaodong Jian; Jinrong Jiang; Kangjun Chen; Qian Yang; et al. (Advances in Atmospheric Sciences, 2020)
A 61-year (1958–2018) global eddy-resolving dataset for phase 2 of the Ocean Model Intercomparison Project has been produced by the version 3 of Chinese Academy of Science, the State Key Laboratory of Numerical Modeling for Atmospheric Sciences and Geophysical Fluid Dynamics/Institute of Atmospheric Physics (LASG/IAP) Climate system Ocean Model (CAS-LICOM3). The monthly and a part of the surface daily data in this study can be accessed on the Earth System Grid Federation (ESGF) node. Besides the details of the model and experiments, the evolutions and spatial patterns of large-scale and mesoscale features are also presented. The mesoscale features are reproduced well in the high-resolution simulation, as the mesoscale activities can contribute up to 50% of the total SST variability in eddy-rich regions. Also, the large-scale circulations are remarkably improved compared with the low-resolution simulation, such as the climatological annual mean SST (the RMSE is reduced from 0.59°C to 0.47°C, globally) and the evolution of Atlantic Meridional Overturning Circulation. The preliminary evaluation also indicates that there are systematic biases in the salinity, the separation location of the western boundary currents, and the magnitude of eddy kinetic energy. All these biases are worthy of further investigation.

Synthesis and biological evaluation of a new series of 1-aryl-3-[4-(pyridin-2-ylmethoxy)phenyl]urea derivatives as new anticancer agents - Jian Feng; Tai Li; Shishao Liang; Chuanming Zhang; Xiaoyu Tan; Ning Ding; Xin Wang; Xiaoping Liu; Chun Hu (Medicinal Chemistry Research, 2020)

Variation of biogeochemical cycle of riverine dissolved inorganic carbon and silicon with the cascade damming - Haojun Deng; Zhen Tao; Quanzhou Gao; Ling Yao; Yong Feng; Yinhua Li; Jian Ding; Zhengang Wang; Xiaoxi Lyu; Peng Xu (Environmental Science and Pollution Research, 2020)

Astrocytic GABAB Receptors in Mouse Hippocampus Control Responses to Behavioral Challenges through Astrocytic BDNF - Ji-Hong Liu; Ze-Lin Li; Yi-Si Liu; Huai-De Chu; Neng-Yuan Hu; Ding-Yu Wu; Lang Huang; Shu-Ji Li; Xiao-Wen Li; Jian-Ming Yang; Tian-Ming Gao (Neuroscience Bulletin, 2020)

Hepatitis B virus X protein promotes liver cell pyroptosis under oxidative stress through NLRP3 inflammasome activation - Wen-hui Xie; Jian Ding; Xiao-xia Xie; Xiao-huang Yang; Xiao-Fan Wu; Zhi-xin Chen; Qi-lan Guo; Wen-yu Gao; Xiao-zhong Wang; Dan Li (Inflammation Research, 2020)
Objective Hepatitis B virus X protein (HBx) is a pivotal factor for HBV-induced hepatitis. Herein, we sought to investigate HBx-mediated NLR pyrin domain containing 3 (NLRP3) inflammasome activation and pyroptosis under oxidative stress. Methods The effect of HBx on the NLRP3 inflammasome was analyzed by enzyme-linked immunosorbent assays, quantitative reverse transcription-polymerase chain reaction, western blotting, and immunofluorescence in hepatic HL7702 cells. Pyroptosis was evaluated by western blotting, lactate dehydrogenase release, propidium iodide staining, and transmission electron microscopy. NLRP3 expression in the inflammasome from liver tissues was assessed by immunohistochemistry. Results In hydrogen peroxide (H 2 O 2 )-stimulated HL7702 cells, HBx triggered the release of pro-inflammatory mediators apoptosis-associated speck-like protein containing a CARD (ASC), interleukin (IL)-1β, IL-18, and high-mobility group box 1 (HMGB1); activated NLRP3; and initiated pro-inflammatory cell death (pyroptosis). HBx localized to the mitochondria, where it induced mitochondrial damage and production of mitochondrial reactive oxygen species (mitoROS). Treatment of HL7702 cells with a mitoROS scavenger attenuated HBx-induced NLRP3 activation and pyroptosis. Expression levels of NLRP3, ASC, and IL-1β in liver tissues from patients were positively correlated with HBV DNA concentration. Conclusions The NLRP3 inflammasome was activated by elevated mitoROS levels and mediated HBx-induced liver inflammation and hepatocellular pyroptosis under H 2 O 2 -stress conditions.

The Family of Peanut Fatty Acid Desaturase Genes and a Functional Analysis of Four ω-3 AhFAD3 Members - Zhenying Peng; Jian Ruan; Haiying Tian; Lei Shan; Jingjing Meng; Feng Guo; Zhimeng Zhang; Hong Ding; Shubo Wan; Xinguo Li (Plant Molecular Biology Reporter, 2020)
The synthesis of α-linolenic acid (ALA) requires the activity of ω-3 fatty acid desaturases (ω-3 FADs). The quality of peanut oil would be much improved if the content of ALA could be increased. A scan of the peanut genome revealed that it harbored 36 FAD genes, mapping to 16 of the species’ 20 chromosomes. A phylogenetic analysis concluded that these genes belonged to six sub-families, namely stearoyl-acyl-acyl carrier protein desaturases ( SAD ), FAD2 , FAD3 , FAD4/5 , FAD6 and FAD7/8 . Of these, FAD3 and FAD7/8 encoded ω-3 FADs, while genes belonging to the other four sub-families encoded ω-6 FADs. Based on RNA-Seq data, each of the 36 FAD genes was shown to be transcribed in non-stressed plants, but there was variation between them with respect to which organs they were transcribed in. Four ω-3 AhFAD3 genes were functionally characterized; when expressed in Arabidopsis thaliana protoplasts, each was localized mainly in the endoplasmic reticulum, while within peanut, the genes were more strongly transcribed in the developing seed than in either the root or the leaf. When constitutively expressed in Arabidopsis thaliana , both the total fatty acid content of the seed and the relative contribution of ALA were increased. The transgenic seedlings also exhibited an improved level of survival when challenged by salinity stress.

Mapping and characterization of major QTL for spike traits in common wheat - Cheng-Hao Kuang; Xiao-Fang Zhao; Ke Yang; Zhi-Peng Zhang; Li Ding; Zhi-En Pu; Jian Ma; Qian-Tao Jiang; Guo-Yue Chen; Ji-Rui Wang; Yu-Ming Wei; You-Liang Zheng; et al. (Physiology and Molecular Biology of Plants, 2020)

Plant abiotic stress response and nutrient use efficiency - Zhizhong Gong; Liming Xiong; Huazhong Shi; Shuhua Yang; Luis R. Herrera-Estrella; Guohua Xu; Dai-Yin Chao; Jingrui Li; Peng-Yun Wang; Feng Qin; Jijang Li; Yanglin Ding; et al. (Science China Life Sciences, 2020)

Illumina MiSeq sequencing and network analysis the distribution and co-occurrence of bacterioplankton in Danjiangkou Reservoir, China - Zhao-Jin Chen; Ge Xu; Chuan-Yu Ding; Bao-Hai Zheng; Yan Chen; Hui Han; Yu-Ying Li; Jian-Wei Shi; Lan-Qun Hu (Archives of Microbiology, 2020)

Shear strength and mesoscopic character of undisturbed loess with sodium sulfate after dry-wet cycling - Jian Xu; Yanfeng Li; Songhe Wang; Qinze Wang; Jiulong Ding (Bulletin of Engineering Geology and the Environment, 2020)

Morphological characteristics and genetic diversity of Colletotrichum horii infecting persimmon tree in China - Quan-en Deng; Xiang-yang Ding; Jian-an Li; Lin-kai Cui; Jian-qiang Xu (European Journal of Plant Pathology, 2020)

Colonization and Probiotic Effect of Metschnikowia sp. C14 in the Intestine of Juvenile Sea Cucumber, Apostichopus japonicus - Ming Li; Pengyun Bao; Jian Song; Jianfeng Ding; Yubin Liu; Yuexin Ma (Journal of Ocean University of China, 2020)

Correction to: Identification and validation of a major and stably expressed QTL for spikelet number per spike in bread wheat - Jian Ma; Puyang Ding; Jiajun Liu; Ting Li; Yaya Zou; Ahsan Habib; Yang Mu; Huaping Tang; Qiantao Jiang; Yaxi Liu; Guoyue Chen; Jirui Wang; et al. (Theoretical and Applied Genetics, 2020)

Flag leaf size and posture of bread wheat: genetic dissection, QTL validation and their relationships with yield-related traits - Jian Ma; Yang Tu; Jing Zhu; Wei Luo; Hang Liu; Cong Li; Shuiqin Li; Jiajun Liu; Puyang Ding; Ahsan Habib; Yang Mu; Huaping Tang; et al. (Theoretical and Applied Genetics, 2020)

Identification and validation of a major and stably expressed QTL for spikelet number per spike in bread wheat - Jian Ma; Puyang Ding; Jiajun Liu; Ting Li; Yaya Zou; Ahsan Habib; Yang Mu; Huaping Tang; Qiantao Jiang; Yaxi Liu; Guoyue Chen; Jirui Wang; et al. (Theoretical and Applied Genetics, 2019)

Trace metals in aquatic environments of a mangrove ecosystem in Nansha, Guangzhou, South China: pollution status, sources, and ecological risk assessment - Yingjie Chen; Huanfang Huang; Yang Ding; Wenwen Chen; Jie Luo; Hui Li; Jian Wu; Wei Chen; Shihua Qi (Environmental Monitoring and Assessment, 2019)

Snowmelt modeling using two melt-rate models in the Urumqi River watershed, Xinjiang Uyghur Autonomous Region, China - Muattar Saydi; Jian-li Ding; Vasit Sagan; Yan Qin (Journal of Mountain Science, 2019)

Eogenetic Karst in Interbedded Carbonates and Evaporites and Its Impact on Hydrocarbon Reservoir: A New Case from Middle Triassic Leikoupo Formation in Sichuan Basin, Southwest China - Hong Liu; Xiucheng Tan; Ling Li; Xiong Ding; Jian Cao; Guang Yang; Teng Ma (Journal of Earth Science, 2019)

Protective effect of isoliquiritigenin against cerebral injury in septic mice via attenuation of NF-κB - Peng Zou; Hong-Ming Ji; Jian-Wei Zhao; Xin-Min Ding; Zi-Gang Zhen; Xuan Zhang; Xiao-Qi Nie; Li-Xiong Xue (Inflammopharmacology, 2019)

A new pregnane steroid from cultures of Aspergillus versicolor - Jian-Hai Ding; Zhang-Gui Ding; Jiang-Yuan Zhao; Ming-Gang Li; Dong-Bao Hu; Xian-Jun Jiang; Dong-Sheng Zhou; Fei Wang; Meng-Liang Wen (Natural Product Research, 2019)

A single-base change at a splice site in Wx-A1 caused incorrect RNA splicing and gene inactivation in a wheat EMS mutant line - Mi Luo; Jinjin Ding; Yu Li; Huaping Tang; Pengfei Qi; Jian Ma; Jirui Wang; Guoyue Chen; Zhien Pu; Wei Li; Zhongyi Li; Wendy Harwood; et al. (Theoretical and Applied Genetics, 2019)

Biotransformation of 20( R )-panaxatriol by the fungus Aspergillus flavus Link AS 3.3950 - Jian Lin Li; Peiyu Ding; Baocheng Jiang; Min Yang; Jie Ren; Yan Song; Guangtong Chen (Natural Product Research, 2019)

δ-Opioid Receptor Activation Attenuates the Oligomer Formation Induced by Hypoxia and/or α-Synuclein Overexpression/Mutation Through Dual Signaling Pathways - Tao Chen; Qinyu Wang; Dongman Chao; Terry C. Xia; Shiying Sheng; Zhuo-Ri Li; Jian-Nong Zhao; Guo-Qiang Wen; Guanghong Ding; Ying Xia (Molecular Neurobiology, 2019)

Wave parameters retrieval for dual-polarization C-band synthetic aperture radar using a theoretical-based algorithm under cyclonic conditions - Yingying Ding; Juncheng Zuo; Weizeng Shao; Jian Shi; Xinzhe Yuan; Jian Sun; Jiachen Hu; Xiaofeng Li (Acta Oceanologica Sinica, 2019)

The antitoxin MqsA homologue in Pseudomonas fluorescens 2P24 has a rewired regulatory circuit through evolution - Yong Wang; Si‐Ping Zhang; Meng‐Yuan Zhang; Megan L. Kempher; Ding‐Ding Guo; Jian‐Ting Han; Xuanyu Tao; Yi Wu; Li‐Qun Zhang; Yong‐Xing He (Environmental Microbiology, 2019)
Summary The mqsRA operon encodes a toxin–antitoxin pair that was characterized to participate in biofilm and persister cell formation in Escherichia coli . Notably, the antitoxin MqsA possesses a C‐terminal DNA‐binding domain that recognizes the [5’‐AACCT(N) 2‐4 AGGTT‐3′] motif and acts as a transcriptional regulator controlling multiple genes including the general stress response regulator RpoS. However, it is unknown how the transcriptional circuits of MqsA homologues have changed in bacteria over evolutionary time. Here, we found mqsA in Pseudomonas fluorescens ( PfmqsA ) is acquired through horizontal gene transfer and binds to a slightly different motif [5′‐TACCCT(N) 3 AGGGTA‐3′], which exists upstream of the PfmqsRA operon. Interestingly, an adjacent GntR‐type transcriptional regulator, which was termed AgtR, is under negative control of PfMqsA. It was further demonstrated that PfMqsA reduces production of biofilm components through AgtR, which directly regulates the pga and fap operons involved in the synthesis of extracellular polymeric substances. Moreover, through quantitative proteomics analysis, we showed AgtR is a highly pleiotropic regulator that influences up to 252 genes related to diverse processes including chemotaxis, oxidative phosphorylation and carbon and nitrogen metabolism. Taken together, our findings suggest the rewired regulatory circuit of PfMqsA influences diverse physiological aspects of P. fluorescens 2P24 via the newly characterized AgtR.

Dynamic Response for a Submerged Floating Offshore Wind Turbine with Different Mooring Configurations - Yane Li; Conghuan Le; Hongyan Ding; Puyang Zhang; Jian Zhang (Journal of Marine Science and Engineering, 2019)
The paper discusses the effects of mooring configurations on the dynamic response of a submerged floating offshore wind turbine (SFOWT) for intermediate water depths. A coupled dynamic model of a wind turbine-tower-floating platform-mooring system is established, and the dynamic response of the platform, tensions in mooring lines, and bending moment at the tower base and blade root under four different mooring configurations are checked. A well-stabilized configuration (i.e., four vertical lines and 12 diagonal lines with an inclination angle of 30°) is selected to study the coupled dynamic responses of SFOWT with broken mooring lines, and in order to keep the safety of SFOWT under extreme sea-states, the pretension of the vertical mooring line has to increase from 1800–2780 kN. Results show that the optimized mooring system can provide larger restoring force, and the SFOWT has a smaller movement response under extreme sea-states; when the mooring lines in the upwind wave direction are broken, an increased motion response of the platform will be caused. However, there is no slack in the remaining mooring lines, and the SFOWT still has enough stability.

A new guaiane sesquiterpene from cultures of the fungus Fulvifomes kanehirae - Jian-Hai Ding; Zheng-Hui Li; Tao Feng; Ji-Kai Liu (Natural Product Research, 2019)

Two pairs of phenolic enantiomers from the leaves of Eucommia ulmoides Oliver - Jian-Kun Yan; Xu-Liu Shi; Paul Owusu Donkor; Xiu-Mei Gao; Li-Qin Ding; Feng Qiu (Natural Product Research, 2019)

A new tremulane sesquiterpenoid from the fungus Irpex lacteus - Jian-Hai Ding; Zheng-Hui Li; Tao Feng; Ji-Kai Liu (Natural Product Research, 2019)

A new cyclohexenone from the tin mine tailings-derived fungus Aspergillus flavus YIM DT 10012 - Wei-Xun Chunyu; Jiang-Yuan Zhao; Zhang-Gui Ding; Xiu-Lin Han; Yong-Xia Wang; Jian-Hai Ding; Fei Wang; Ming-Gang Li; Meng-Liang Wen (Natural Product Research, 2019)

Role of prefrontal cortex in the extinction of drug memories - Wen-Hua Zhang; Ke-Xin Cao; Zeng-Bo Ding; Jian-Li Yang; Bing-Xing Pan; Yan-Xue Xue (Psychopharmacology, 2019)

Erratum to: The clinical and genetic characteristics in children with mitochondrial disease in China - Fang Fang; Zhimei Liu; Hezhi Fang; Jian Wu; Danmin Shen; Suzhen Sun; Changhong Ding; Tongli Han; Yun Wu; Junlan Lv; Lei Yang; Shufang Li; et al. (Science China Life Sciences, 2018)

Arctic Climate Changes Based on Historical Simulations (1900‒2013) with the CAMS-CSM - Ting Wei; Jian Li; Xinyao Rong; Wenjie Dong; Bingyi Wu; Minghu Ding (Journal of Meteorological Research, 2018)

A novel sesquiterpene derivative with a seven-membered B ring from Illigera aromatica - Jian-Wei Dong; Le Cai; Xue-Jiao Li; Yan Shu; Jia-Peng Wang; Zhong-Tao Ding (Natural Product Research, 2018)

A 55 K SNP array-based genetic map and its utilization in QTL mapping for productive tiller number in common wheat - Jiajun Liu; Wei Luo; Nana Qin; Puyang Ding; Han Zhang; Congcong Yang; Yang Mu; Huaping Tang; Yaxi Liu; Wei Li; Qiantao Jiang; Guoyue Chen; et al. (Theoretical and Applied Genetics, 2018)

Genome-wide identification and characterization of ALTERNATIVE OXIDASE genes and their response under abiotic stresses in Camellia sinensis (L.) O. Kuntze - Chang-Qing Ding; Sophia Ng; Lu Wang; Yu-Chun Wang; Na-Na Li; Xin-Yuan Hao; Jian-Ming Zeng; Xin-Chao Wang; Ya-Jun Yang (Planta, 2018)

Screening of candidate gene responses to cadmium stress by RNA sequencing in oilseed rape (Brassica napus L.) - Yiran Ding; Hongju Jian; Tengyue Wang; Feifei Di; Jia Wang; Jiana Li; Liezhao Liu (Environmental Science and Pollution Research, 2018)

A novel phenylspirodrimane dimer from cultures of the fungus Stachybotrys chartarum - Zhang-Gui Ding; Jiang-Yuan Zhao; Jian-Hai Ding; Wei-Xun Chunyu; Ming-Gang Li; Shao-Jie Gu; Fei Wang; Meng-Liang Wen (Natural Product Research, 2018)

A new cadinane sesquiterpenoid from cultures of the Basidiomycete Panus conchatus - Jian-Hai Ding; Zheng-Hui Li; Tao Feng; Ji-Kai Liu (Natural Product Research, 2018)

The Dysfunction of the Cerebellum and Its Cerebellum-Reward-Sensorimotor Loops in Chronic Spontaneous Urticaria - Yuming Wang; Jiliang Fang; Ping Song; Yan Bao; Wenwen Song; Jiao Liu; Courtney Lang; Kristen Jorgenson; Minyoung Jung; Dong Shen; Shasha Li; Ruirui Sun; et al. (The Cerebellum, 2018)

Neutrophil-to-Lymphocyte Ratio Is an Independent Predictor of 30-Day Mortality of Intracerebral Hemorrhage Patients: a Validation Cohort Study - Fei Wang; Li Wang; Ting-ting Jiang; Jian-jun Xia; Feng Xu; Li-juan Shen; Wen-hui Kang; Yong Ding; Li-xia Mei; Xue-feng Ju; Shan-you Hu; Xiao Wu (Neurotoxicity Research, 2018)

Two new polyols from cultures of the fungus Daedaleopsis tricolor - Jiang-Yuan Zhao; Jian-Hai Ding; Zheng-Hui Li; Tao Feng; Hong-Bin Zhang; Ji-Kai Liu (Natural Product Research, 2018)

The key gluconeogenic gene PCK1 is crucial for virulence of Botrytis cinerea via initiating its conidial germination and host penetration - Jian‐Kang Liu; Hao‐Wu Chang; Yue Liu; Yu (Haity) Qin; Yu‐Han Ding; Lan Wang; Yue Zhao; Ming‐Zhe Zhang; Sheng‐Nan Cao; Le‐Tao Li; Wei Liu; Gui‐Hua Li; et al. (Environmental Microbiology, 2018)
Summary The process of initiation of host invasion and survival of some foliar phytopathogenic fungi in the absence of external nutrients on host leaf surfaces remains obscure. Here, we demonstrate that gluconeogenesis plays an important role in the process and nutrient‐starvation adaptation before the pathogen host invasion. Deletion of phosphoenolpyruvate c arboxy k inase gene BcPCK1 in gluconeogenesis in Botrytis cinerea , the causative agent of grey mould, resulted in the failure of the Δ Bcpck1 mutant conidia to germinate on hard and hydrophobic surface and penetrate host cells in the absence of glucose, reduction in conidiation and slow conidium germination in a nutrient‐rich medium. The wild‐type and Δ Bcpck1 conidia germinate similarly in the presence of glucose (higher concentration) as the sole carbon source. Conidial glucose‐content should reach a threshold level to initiate germination and host penetration. Infection structure formation by the mutants displayed a glucose‐dependent fashion, which corresponded to the mutant virulence reduction. Exogenous glucose or complementation of BcPCK1 completely rescued all the developmental and virulence defects of the mutants. Our findings demonstrate that BcPCK1 plays a crucial role in B. cinerea pathogenic growth and virulence, and provide new insights into gluconeogenesis mediating pathogenesis of plant fungal pathogens via initiation of conidial germination and host penetration.

A new cyclic dipeptide from cultures of Coprinus plicatilis - Jiang-Yuan Zhao; Jian-Hai Ding; Zheng-Hui Li; Tao Feng; Hong-Bin Zhang; Ji-Kai Liu (Natural Product Research, 2018)

Microsatellite records for volume 10, issue 1 - Ai-Qing Yu; Chengxin Fu; Chongbo He; Fei Liu; Guo-Hua Ding; Hongman Hou; Jian Zhao; Jianmin Yang; Jiansheng Wang; Kun-ci Chen; Lan-lan Zhang; Pan Li; et al. (Conservation Genetics Resources, 2018)

ALDH2 genes are negatively correlated with natural deastringency in Chinese PCNA persimmon (Diospyros kaki Thunb.) - Jun-Chi Xu; Jin-Ge Ding; Jian-Ping Gan; Rong-Li Mo; Li-Qing Xu; Qing-Lin Zhang; Zheng-Rong Luo (Tree Genetics & Genomes, 2017)

Comparative transcriptome analysis of lipid biosynthesis in seeds and non-seed tissues of sea buckthorn - Jian Ding; Li Wang; Chengjiang Ruan (Genes & Genomics, 2017)

Seasonal variations of organic carbon and nitrogen in the upper basins of Yangtze and Yellow Rivers - Xiang-ying Li; Yong-jian Ding; Tian-ding Han; Jian-zhong Xu; Shi-chang Kang; Qing-bai Wu; Mika Sillanpää; Zhong-bo Yu; Cong-rong Yu (Journal of Mountain Science, 2017)

The clinical and genetic characteristics in children with mitochondrial disease in China - Fang Fang; Zhimei Liu; Hezhi Fang; Jian Wu; Danmin Shen; Suzhen Sun; Changhong Ding; Tongli Han; Yun Wu; Junlan Lv; Lei Yang; Shufang Li; et al. (Science China Life Sciences, 2017)

Carboniferous Alaskan-type complex along the Sino–Mongolian boundary, southern margin of the Central Asian Orogenic Belt - Yuruo Shi; Linlin Li; Alfred Kröner; Jing Ding; Wei Zhang; Zengbao Huang; Ping Jian (Acta Geochimica, 2017)

Work stress, family stress and asthma: a cross-sectional study among women in China - Adrian Loerbroks; Hui Ding; Wei Han; Hong Wang; Jiang-Ping Wu; Liu Yang; Peter Angerer; Jian Li (International Archives of Occupational and Environmental Health, 2017)

Exploring the possible binding mode of trisubstituted benzimidazoles analogues in silico for novel drug designtargeting Mtb FtsZ - Ding Li; Bo Chi; Wei-Wei Wang; Jin-Ming Gao; Jian Wan (Medicinal Chemistry Research, 2017)

Identification of aberrant DNA methylation involved in chemoradiation-resistant HCT116 cells via methylation-specific microarray - Wei Xiong; Yun-Feng Li; Shan Liu; Ting Chen; Hong-Tao Zhang; Zhi-Bin Yang; Ying-Ying Ding; De-Pei Gao; Guan-Shun Wang; Jian Dong (Molecular & Cellular Toxicology, 2016)

Formation of Late Jurassic–Early Cretaceous metamorphic core complexes in Northeast China: insight from a structural study of the Yiwulüshan ductile detachment zone - Jian Bo Li; Tao Wang; Lei Guo; Zhi Xia Ouyang; Tao Zeng; Yuan Jun Ding; Ying Zhang (International Geology Review, 2016)

A disputed evidence on obesity: comparison of the effects of Rcan2−/− and Rps6kb1−/− mutations on growth and body weight in C57BL/6J mice - Jing Zhao; Shi-wei Li; Qian-qian Gong; Ling-cui Ding; Ye-cheng Jin; Jian Zhang; Jian-gang Gao; Xiao-yang Sun (Journal of Zhejiang University-SCIENCE B, 2016)

Hypocrol A, a new tyrosol derivative from a sponge-derived strain of the fungus Hypocrea koningii - Li-Jian Ding; Wei Yuan; Ying-Xin Li; Xiao-Jian Liao; Huan Sun; Qi Peng; Bing-Nan Han; Hou-Wen Lin; Zhi-Yong Li; Fan Yang; Shi-Hai Xu (Natural Product Research, 2016)

A new flavone C -glycoside and a new bibenzyl from Bulbophyllum retusiusculum - Ming-Hui Yang; Yun-Shan Fang; Le Cai; Ying Li; Jian-Wei Dong; Tian-Peng Yin; Cai-Li Huang; Zhong-Tao Ding (Natural Product Research, 2016)

Synthesis and potential anticonvulsant activity of new aryl sulfonyl semicarbazide derivatives - Yousong Nie; Min Zhong; Zhiyuan Jiang; Jian Sun; Yangguang Gao; Fei Ding; Hang Li; Yongmin Zhang; Xianran He (Medicinal Chemistry Research, 2016)

Cholangiocarcinoma-derived exosomes inhibit the antitumor activity of cytokine-induced killer cells by down-regulating the secretion of tumor necrosis factor-α and perforin - Jiong-huang Chen; Jian-yang Xiang; Guo-ping Ding; Li-ping Cao (Journal of Zhejiang University-SCIENCE B, 2016)

Combinatorial enzymatic digestion with thermolysin and collagenase type I improved the isolation and culture effects of hair cell progenitors from rat cochleae - Yong-li Song; Ke-yong Tian; Wen-juan Mi; Peng Han; Zhong-jia Ding; Yang Qiu; Fu-quan Chen; Jian-jua Qiu (In Vitro Cellular & Developmental Biology - Animal, 2016)

Impacts of snow disaster on meat production and adaptation: an empirical analysis in the yellow river source region - Yi-ping Fang; Chen Zhao; Yong-jian Ding; Da-he Qin; Jia-li Huang (Sustainability Science, 2016)

Microsatellite records for volume 8, issue 1 - Maria Cristina Arias; Stéphane Aulagnier; Erin F. Baerwald; Robert M. R. Barclay; Jacqueline Silva Batista; Rochelle R. Beasley; Rodrigo A. Bezerra; Frédéric Blanc; Eli S. Bridge; Maria Teresa Cabria; Lívia Izabela Caputo; Jie Chen; et al. (Conservation Genetics Resources, 2016)

Erratum to: Microsatellite records for volume 7, issue 4 - Rose Komugisha Basiita; J. Henrich Bruggemann; Nianhui Cai; Conchi Cáliz-Campal; Chen Chen; Jiawei Chen; L. Cizek; Pedro J. Cordero; Deborah A. Dawson; Yandong Ding; L. Drag; Anan Duan; et al. (Conservation Genetics Resources, 2016)

Simulation of the interface between the Indian summer monsoon and the East Asian summer monsoon: Intercomparison between MPI-ESM and ECHAM5/MPI-OM - Yiran Guo; Jie Cao; Hui Li; Jian Wang; Yuchao Ding (Advances in Atmospheric Sciences, 2016)

Advanced oxidation protein products induce chondrocyte apoptosis via receptor for advanced glycation end products-mediated, redox-dependent intrinsic apoptosis pathway - Qian Wu; Zhao-Ming Zhong; Si-Yuan Zhu; Cong-Rui Liao; Ying Pan; Ji-Huan Zeng; Shuai Zheng; Ruo-Ting Ding; Qing-Song Lin; Qing Ye; Wen-Bin Ye; Wei Li; et al. (Apoptosis, 2016)

Associations of hypoxia inducible factor-1α gene polymorphisms with susceptibility to digestive tract cancers: a case–control study and meta-analysis - Zhi-Hai Ni; Xian-Jun Liang; Jing-Gang Mo; Yi Zhang; Jian-Hua Liang; Yu-Sha Yang; Yong Zhou; Zhao-Hua Li; Jian-Liang Zhang; Yin-Lu Ding; Peng Zhang; Jin-Qing Wang (Genes & Genomics, 2015)

Rice grassy stunt virus nonstructural protein p5 serves as a viral suppressor of RNA silencing and interacts with nonstructural protein p3 - Chao Zhang; Xiao-juan Liu; Kang-cheng Wu; Lu-Ping Zheng; Zuo-mei Ding; Fei Li; Peng Zou; Liang Yang; Jian-guo Wu; Zu-jian Wu (Archives of Virology, 2015)

Over-nutrient environment during both prenatal and postnatal development increases severity of islet injury, hyperglycemia, and metabolic disorders in the offspring - Lei Li; Jing Xue; Hongyan Li; Jian Ding; Yanyun Wang; Xietong Wang (Journal of Physiology and Biochemistry, 2015)

Effect of salt treatment on growth, isoenzymes and metabolites of Andrographis paniculata (Burm. f.) Nees - Yan-hua Shao; Jun-li Gao; Xiang-wei Wu; Qian Li; Jian-gang Wang; Ping Ding; Xiao-ping Lai (Acta Physiologiae Plantarum, 2015)

The influence of natural and human factors in the shrinking of the Ebinur Lake, Xinjiang, China, during the 1972–2013 period - Fei Zhang; Tashpolat Tiyip; Verner Carl Johnson; Hsiang-te Kung; Jian-li Ding; Qian Sun; Mei Zhou; Ardak Kelimu; Ilyas Nurmuhammat; Ngai Weng Chan (Environmental Monitoring and Assessment, 2015)

Retraction Note to: Characterization of cancer stem-like cells in the side population cells of human gastric cancer cell line MKN-45 - Hai-hong Zhang; Ai-zhen Cai; Xue-ming Wei; Li Ding; Feng-zhi Li; Ai-ming Zheng; Da-jiang Dai; Rong-rong Huang; Hou-jun Cao; Hai-yang Zhou; Jian-mei Wang; Xue-jing Wang; et al. (Journal of Zhejiang University-SCIENCE B, 2014)

Potential of Mesenchymal Stem Cells by Adenovirus-Mediated Erythropoietin Gene Therapy Approaches for Bone Defect - Chen Li; Jian Ding; Liming Jiang; Ce Shi; Shilei Ni; Han Jin; Daowei Li; Hongchen Sun (Cell Biochemistry and Biophysics, 2014)

The operating performance of a biotrickling filter with Lysinibacillus fusiformis for the removal of high-loading gaseous chlorobenzene - Zhao-Xia Li; Bai-Ren Yang; Jian-Xiang Jin; Yi-Chen Pu; Cheng Ding (Biotechnology Letters, 2014)

Neuroprotective effect of schizandrin A on oxygen and glucose deprivation/reperfusion-induced cell injury in primary culture of rat cortical neurons - Cai-Ping Wang; Gui-Cai Li; Yun-Wei Shi; Xiao-Chuan Zhang; Jian-Long Li; Zhi-Wei Wang; Fei Ding; Xin-Miao Liang (Journal of Physiology and Biochemistry, 2014)

Prediction of protein structural classes based on feature selection technique - Hui Ding; Hao Lin; Wei Chen; Zi-Qiang Li; Feng-Biao Guo; Jian Huang; Nini Rao (Interdisciplinary Sciences: Computational Life Sciences, 2014)

Clinical Factors Associated With the Diagnosis and Progression of Diabetic Nephropathy - Shuang Liang; Qian Li; Han-Yu Zhu; Jian-Hui Zhou; Rui Ding; Xiang-Mei Chen; Guang-Yan Cai (Cell Biochemistry and Biophysics, 2014)

Differential role of Rac in the basolateral amygdala and cornu ammonis 1 in the reconsolidation of auditory and contextual Pavlovian fear memory in rats - Ping Wu; Zeng-Bo Ding; Shi-Qiu Meng; Hao-Wei Shen; Shi-Chao Sun; Yi-Xiao Luo; Jian-Feng Liu; Lin Lu; Wei-Li Zhu; Jie Shi (Psychopharmacology, 2014)

Long-Term Outcome of Sensorineural Hearing Loss in Nasopharyngeal Carcinoma Patients: Comparison Between Treatment with Radiotherapy Alone and Chemoradiotherapy - Yumei Wei; Tao Zhou; Jian Zhu; Yi Zhang; Mingping Sun; Xiuping Ding; Dongqing Wang; Hongsheng Li; Baosheng Li (Cell Biochemistry and Biophysics, 2014)

Anterolateral minithoracotomy versus median sternotomy for mitral valve disease: a meta-analysis - Chao Ding; Da-ming Jiang; Kai-yu Tao; Qun-jun Duan; Jie Li; Min-jian Kong; Zhong-hua Shen; Ai-qiang Dong (Journal of Zhejiang University-SCIENCE B, 2014)

Overexpression, purification, molecular characterization and the effect on tumor growth of ribosomal protein L22 from the Giant Panda (Ailuropoda melanoleuca) - Jian Li; Yiling Hou; Xiang Ding; Wanru Hou; Bo Song; Yichun Zeng (Molecular Biology Reports, 2014)

Origins of evaporites in the Middle Triassic Leikoupo Formation of the Sichuan Basin, southwest China and their geological implications - Ling Li; Xiucheng Tan; Jian Cao; Chun Zou; Xiong Ding; Guang Yang; Danling Ying (Carbonates and Evaporites, 2014)

A simple and effective method for the isolation of inner cell mass samples from human blastocysts for gene expression analysis - Jian Xu; Yan Li; Yanwen Xu; Chenhui Ding; Tao Li; Canquan Zhou (In Vitro Cellular & Developmental Biology - Animal, 2014)

MicroRNA-22 targeting CBP protects against myocardial ischemia–reperfusion injury through anti-apoptosis in rats - Jian Yang; Lihua Chen; Jun Yang; Jiawang Ding; Song Li; Hui Wu; Jing Zhang; Zhixing Fan; Wusong Dong; Xinxin Li (Molecular Biology Reports, 2014)

Surface energy balance measurements over a banana plantation in South China - Zhangwei Ding; Zhiping Wen; Renguang Wu; Zhenchao Li; Jianjun Zhu; Weibiao Li; Maoqiu Jian (Theoretical and Applied Climatology, 2013)

Prevalence of hepatitis B virus and hepatitis C virus in patients with human immunodeficiency virus infection in central China - Xi Chen; Jian-Mei He; Li-Sha Ding; Guo-Qiang Zhang; Xiao-Bai Zou; Jun Zheng (Archives of Virology, 2013)

Potential hepatotoxicity of geniposide, the major iridoid glycoside in dried ripe fruits of Gardenia jasminoides (Zhi-zi) - Yue Ding; Tong Zhang; Jian-sheng Tao; Li-ying Zhang; Jian-rong Shi; Guang Ji (Natural Product Research, 2013)

Inhibition of autophagy enhances anticancer effects of bevacizumab in hepatocarcinoma - Xian-ling Guo; Ding Li; Kai Sun; Jin Wang; Yan Liu; Jian-rui Song; Qiu-dong Zhao; Shan-shan Zhang; Wei-jie Deng; Xue Zhao; Meng-chao Wu; Li-xin Wei (Journal of Molecular Medicine, 2013)

RETRACTED ARTICLE: Characterization of cancer stem-like cells in the side population cells of human gastric cancer cell line MKN-45 - Hai-hong Zhang; Ai-zhen Cai; Xue-ming Wei; Li Ding; Feng-zhi Li; Ai-ming Zheng; Da-jiang Dai; Rong-rong Huang; Hou-jun Cao; Hai-yang Zhou; Jian-mei Wang; Xue-jing Wang; et al. (Journal of Zhejiang University-SCIENCE B, 2013)

Curcumin Ameliorates the Neurodegenerative Pathology in A53T α-synuclein Cell Model of Parkinson’s Disease Through the Downregulation of mTOR/p70S6K Signaling and the Recovery of Macroautophagy - Tian-Fang Jiang; Ying-Jie Zhang; Hai-Yan Zhou; Hong-Mei Wang; Li-Peng Tian; Jun Liu; Jian-Qing Ding; Sheng-Di Chen (Journal of Neuroimmune Pharmacology, 2013)

Perifosine Induces Cell Apoptosis in Human Osteosarcoma Cells: New Implication for Osteosarcoma Therapy? - Chen Yao; Jian-jun Wei; Zu-yu Wang; Hui-min ding; Dong Li; Shi-chang Yan; Yong-jiang Yang; Zhang-ping Gu (Cell Biochemistry and Biophysics, 2013)

Selection of an Effective Small Interference RNA to Silence Myostatin Gene Expression in Sheep Fibroblast Cells - Jian Lu; Dan Sun; Lingyang Xu; Guobin Lu; Fuping Zhao; Caihong Wei; Li Zhang; Jiatong Ding; Bichun Li; Lixin Du (Biochemical Genetics, 2012)

TNFAIP1 interacts with KCTD10 to promote the degradation of KCTD10 proteins and inhibit the transcriptional activities of NF-κB and AP-1 - Xiang Hu; Feng Yan; Fangmei Wang; Zijian Yang; Ling Xiao; Li Li; Shuanglin Xiang; Jianlin Zhou; Xiaofeng Ding; Jian Zhang (Molecular Biology Reports, 2012)

A fully automatic registration approach based on contour and SIFT for HJ-1 images - XiLiang Ni; ChunXiang Cao; Lin Ding; Tao Jiang; Hao Zhang; HuiCong Jia; GuangHe Li; Jian Zhao; Wei Chen; Wei Ji; Min Xu; MengXu Gao; et al. (Science China Earth Sciences, 2012)

Erratum to: Comparative codon usage between the three main viruses in pestivirus genus and their natural susceptible livestock - Jian-hua Zhou; Zong-liang Gao; Jie Zhang; Hao-tai Chen; Zygmunt Pejsak; Li-na Ma; Yao-zhong Ding; Yong-sheng Liu (Virus Genes, 2012)

Molecular and cytological evidences for the natural wheatgrass hybrids occurrence and origin in west China - Jian Zeng; Xing Fan; Hai-Qin Zhang; Li-Na Sha; Hou-Yang Kang; Li Zhang; Rui-Wu Yang; Chun-Bang Ding; Yong-Hong Zhou (Genes & Genomics, 2012)

Cloning and characterization of miRNAs from maize seedling roots under low phosphorus stress - Zhiming Zhang; Haijian Lin; Yaou Shen; Jian Gao; Kui Xiang; Li Liu; Haiping Ding; Guangsheng Yuan; Hai Lan; Shufeng Zhou; Maojun Zhao; Shibin Gao; et al. (Molecular Biology Reports, 2012)

Screening for significant atherosclerotic renal artery stenosis with a regression model in patients undergoing transradial coronary angiography/intervention - Li-jin Pu; Ying Shen; Rui-yan Zhang; Qi Zhang; Lin Lu; Feng-hua Ding; Jian Hu; Zheng-kun Yang; Wei-feng Shen (Journal of Zhejiang University-SCIENCE B, 2012)

Pseudolaric acid B-driven phosphorylation of c-Jun impairs its role in stabilizing HIF-1alpha: a novel function-converter model - Bing Yu; Mei-Hong Li; Wei Wang; Ying-Qing Wang; Yi Jiang; Sheng-Ping Yang; Jian-Min Yue; Jian Ding; Ze-Hong Miao (Journal of Molecular Medicine, 2012)

Sphingosine 1-phosphate acts as an activator for the porcine Gpr3 of constitutively active G protein-coupled receptors - Bao-le Zhang; Ye Li; Jian-hua Ding; Fu-lu Dong; Yan-jun Hou; Bao-chun Jiang; Fang-xiong Shi; Yin-xue Xu (Journal of Zhejiang University-SCIENCE B, 2012)

Lmx1b can promote the differentiation of embryonic stem cells to dopaminergic neurons associated with Parkinson’s disease - Li-Peng Tian; Shi Zhang; Ying-Jie Zhang; Jian-Qing Ding; Sheng-Di Chen (Biotechnology Letters, 2012)

Comparative the codon usage between the three main viruses in pestivirus genus and their natural susceptible livestock - Jian-hua Zhou; Zong-liang Gao; Jie Zhang; Hao-tai Chen; Zygmunt Pejsak; Li-na Ma; Yao-zhong Ding; Yong-sheng Liu (Virus Genes, 2012)

Phylogeny and molecular evolution of the DMC1 gene within the StH genome species in Triticeae (Poaceae) - Xiao-Li Wang; Xing Fan; Jian Zeng; Li-Na Sha; Hai-Qin Zhang; Hou-Yang Kang; Rui-Wu Yang; Li Zhang; Chun-Bang Ding; Yong-Hong Zhou (Genes & Genomics, 2012)

High mobility group box-1 induces migration of vascular smooth muscle cells via TLR4-dependent PI3K/Akt pathway activation - Jian Yang; Lihua Chen; Jun Yang; Jiawang Ding; Han Rong; Wusong Dong; Xinxin Li (Molecular Biology Reports, 2012)

The monitoring results of electromagnetic radiation of 110-kV high-voltage lines in one urban location in Chongqing P.R. China - Qi-zhong Qin; Yu Chen; Ting-ting Fu; Li Ding; Ling-li Han; Jian-chao Li (Environmental Monitoring and Assessment, 2012)

A new QTL for resistance to Fusarium ear rot in maize - Zhi-Min Li; Jun-Qiang Ding; Rui-Xia Wang; Jia-Fa Chen; Xiao-Dong Sun; Wei Chen; Wei-Bin Song; Hua-Fang Dong; Xiao-Dong Dai; Zong-Liang Xia; Jian-Yu Wu (Journal of Applied Genetics, 2011)

Insulin-like growth factor-1 receptor activation prevents hydrogen peroxide-induced oxidative stress, mitochondrial dysfunction and apoptosis - Chang-Ning Hao; Yong-Jian Geng; Fan Li; Tong Yang; Ding-Feng Su; Jun-Li Duan; Yangxin Li (Apoptosis, 2011)

The cardioprotective effect of fluvastatin on ischemic injury via down-regulation of toll-like receptor 4 - Jun Yang; Xiao-Dong Zhang; Jian Yang; Jia-Wang Ding; Zhao-Qi Liu; Shu-Guo Li; Rui Yang (Molecular Biology Reports, 2011)

Lingo2 variants associated with essential tremor and Parkinson’s disease - Yi-Wen Wu; K. M. Prakash; Tian-Yi Rong; Hui-Hua Li; Qin Xiao; Louis C. Tan; Wing-Lok Au; Jian-qing Ding; Sheng-di Chen; Eng-King Tan (Human Genetics, 2011)

Allelopathic potential of Artemisia frigida and successional changes of plant communities in the northern China steppe - Xue Feng Li; Jian Wang; Ding Huang; Li Xue Wang; Kun Wang (Plant and Soil, 2011)

Analysis of codon usage in Newcastle disease virus - Meng Wang; Yong-sheng Liu; Jian-hua Zhou; Hao-tai Chen; Li-na Ma; Yao-zhong Ding; Wen-qian Liu; Yuan-xing Gu; Jie Zhang (Virus Genes, 2011)

Analysis of codon usage in bovine viral diarrhea virus - Meng Wang; Jie Zhang; Jian-hua Zhou; Hao-tai Chen; Li-na Ma; Yao-zhong Ding; Wen-qian Liu; Yong-sheng Liu (Archives of Virology, 2011)

Hydrogen peroxide and nitric oxide mediate K+/Na+ homeostasis and antioxidant defense in NaCl-stressed callus cells of two contrasting poplars - Jian Sun; Lisi Li; Meiqin Liu; Meijuan Wang; Mingquan Ding; Shurong Deng; Cunfu Lu; Xiaoyang Zhou; Xin Shen; Xiaojiang Zheng; Shaoliang Chen (Plant Cell, Tissue and Organ Culture (PCTOC), 2010)

Assessment of the modulating effects of fructo-oligosaccharides on fecal microbiota using human flora–associated piglets - Jian Shen; Baorang Zhang; Hua Wei; Chuanyan Che; Dezhong Ding; Xiuguo Hua; Peter Bucheli; Linghua Wang; Yixue Li; Xiaoyan Pang; Liping Zhao (Archives of Microbiology, 2010)

CD133+ single cell-derived progenies of colorectal cancer cell line SW480 with different invasive and metastatic potential - Guangqiu Li; Chao Liu; Jian Yuan; Xiaoqin Xiao; Na Tang; Junmei Hao; Hongwei Wang; Xiuwu Bian; Yongjian Deng; Yanqing Ding (Clinical & Experimental Metastasis, 2010)

Identification of p27/KIP1 expression level as a candidate biomarker of response to rapalogs therapy in human cancer - Guang Chen; Na Yang; Xiang Wang; Si-Yuan Zheng; Yi Chen; Lin-Jiang Tong; Yi-Xue Li; Ling-Hua Meng; Jian Ding (Journal of Molecular Medicine, 2010)

Characteristics and sources of atmospheric polycyclic aromatic hydrocarbons (PAHs) in Shanghai, China - Xian Yu Wang; Qing Bo Li; Yong Ming Luo; Qian Ding; Lian Min Xi; Jian Min Ma; Yan Li; Yi Peng Liu; Cui Li Cheng (Environmental Monitoring and Assessment, 2010)

Unique evolutionary pattern of numbers of gramineous NBS–LRR genes - Jing Li; Jing Ding; Wen Zhang; Yuanli Zhang; Ping Tang; Jian-Qun Chen; Dacheng Tian; Sihai Yang (Molecular Genetics and Genomics, 2010)

Improvement of heart function in postinfarct heart failure swine models after hepatocyte growth factor gene transfer: comparison of low-, medium- and high-dose groups - Zhi-jian Yang; Bo Chen; Zhang Sheng; Ding-guo Zhang; En-zhi Jia; Wei Wang; Dong-chao Ma; Tie-bing Zhu; Lian-sheng Wang; Chun-jian Li; Hui Wang; Ke-jiang Cao; et al. (Molecular Biology Reports, 2010)

Valsartan preconditioning protects against myocardial ischemia–reperfusion injury through TLR4/NF-κB signaling pathway - Jian Yang; Hong Jiang; Jun Yang; Jia-Wang Ding; Li-Hua Chen; Song Li; Xiao-Dong Zhang (Molecular and Cellular Biochemistry, 2009)

Reduction in SBPase Activity by Antisense RNA in Transgenic Rice Plants: Effect on Photosynthesis, Growth, and Biomass Allocation at Different Nitrogen Levels - Lingling Feng; Hui Li; Jingmei Jiao; Ding Li; Li Zhou; Jian Wan; Yangsheng Li (Journal of Plant Biology, 2009)

CLOCK/BMAL1 regulates human nocturnin transcription through binding to the E-box of nocturnin promoter - Ran Li; Jiping Yue; Yu Zhang; Lan Zhou; Wei Hao; Jiangang Yuan; Boqin Qiang; Jian M. Ding; Xiaozhong Peng; Ji-Min Cao (Molecular and Cellular Biochemistry, 2008)

Vesicular stomatitis virus matrix protein gene enhances the antitumor effects of radiation via induction of apoptosis - Xiao-Bo Du; Jin-Yi Lang; Jian-Rong XU; You Lu; Yan-Jun Wen; Ju-Mei Zhao; Peng Diao; Zhi-Ping Yuan; Bin Yao; Ling-Yu Fan; Guo-Qing Wang; Li Liu; et al. (Apoptosis, 2008)

Identification of QTL for maize resistance to common smut by using recombinant inbred lines developed from the Chinese hybrid Yuyu22 - Jun-qiang Ding; Xiao-ming Wang; Subhash Chander; Jian-sheng Li (Journal of Applied Genetics, 2008)

Purification and characterization of a psychrophilic glutathione reductase from Antarctic ice microalgae Chlamydomonas sp. Strain ICE-L - Yu Ding; Jin-Lai Miao; Quan-Fu Wang; Zhou Zheng; Guang-You Li; Ji-Chang Jian; Zao-He Wu (Polar Biology, 2007)

Sustainability Evaluation of the Grain for Green Project: From Local People’s Responses to Ecological Effectiveness in Wolong Nature Reserve - Jian-Ying Xu; Li-Ding Chen; Yi-He Lu; Bo-Jie Fu (Environmental Management, 2007)

Expression of Discoidin Domain Receptor 2 (DDR2) Extracellular Domain in Pichia Pastoris and Functional Analysis in Synovial Fibroblasts and NIT3T3 Cells - Wei Zhang; Tianbing Ding; Jian Zhang; Jin Su; Fuyang Li; Xinping Liu; Wenyu Ma; Libo Yao (Molecular and Cellular Biochemistry, 2006)

A new dihydroisocoumarin from the rhizomes of Notopterygium forbesii - Yan-Hui Li; Fan Luo; Shu-Lin Peng; Jian Liang; Li-Sheng Ding (Natural Product Research, 2006)

pp5644 Interacts with phosphatidylinositol-4-phosphate adaptor protein-1 associated protein-1 - Xiao-Xia Ye; Hong Lu; Yao Yu; Ning Ding; Nai-Ling Zhang; Ke-Ke Huo; Da-Fang Wan; Yu-Yang Li; Jian-Ren Gu (Molecular and Cellular Biochemistry, 2005)